Inorganic solid electrolyte composition, sheet for all-solid-state secondary battery and all-solid-state secondary battery, and method for producing sheet for all-solid-state secondary battery and all-solid-state secondary battery
By using compositions containing inorganic solid electrolytes and different types of polymer binders in all-solid secondary batteries, the problem of insufficient interface contact between solid particles is solved, and higher adhesion and lower The interface resistance improves battery performance.
Patent Information
- Application Number
- CN202080073662.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-18
- Filing Date
- 2020-10-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-10-14
AI Technical Summary
The interface contact between solid particles in an all-solid secondary battery is insufficient, resulting in an increase in interface resistance and insufficient adhesion, affecting battery performance.
The inorganic solid electrolyte composition containing metal ions of Group 1 or Group 2 of the periodic table is used to form a constituent layer by using different types of polymer adhesives to ensure sufficient contact and firm bonding between the solid particles.
Effectively suppress the rise of interface resistance, improve the bonding force between solid particles, and improve the circulation characteristics and battery resistance of all-solid secondary batteries.
Smart Images

Figure CN114616710B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an inorganic solid electrolyte composition, a sheet material for an all-solid-state secondary battery and an all-solid-state secondary battery, and a method for manufacturing the sheet material for an all-solid-state secondary battery and the all-solid-state secondary battery. Background Art
[0002] In all-solid-state secondary batteries, all negative electrodes, electrolytes, and positive electrodes are made of solids, which can greatly improve the safety or reliability of batteries using organic electrolytes as a subject. And it can also extend the life. In addition, all-solid-state secondary batteries can be set as a structure in which electrodes and electrolytes are directly arranged and configured in series. Therefore, compared with secondary batteries using organic electrolytes, it can become high energy density, and it is expected to be applied to electric vehicles or large batteries.
[0003] In this all-solid-state secondary battery, it is proposed that any layer of the constituent layers (inorganic solid electrolyte layer, negative electrode active material layer, positive electrode active material layer, etc.) is formed by a material (constituent layer forming material) containing an inorganic solid electrolyte or active material and an adhesive (binder). For example, Patent Document 1 describes a solid electrolyte mixed solution, which includes a solid electrolyte, a first binder insoluble in a non-polar solvent, and a second binder soluble in a non-polar solvent, and the first binder and the second binder have different SP values.
[0004] Previous technical literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 6262503 Summary of the invention
[0007] Technical issues to be solved by the invention
[0008] Since the constituent layers of the all-solid-state secondary battery are formed by solid particles (inorganic solid electrolytes, active materials, conductive aids, etc.), generally speaking, the interface contact state between the solid particles is insufficient and the interface resistance tends to become high, and the bonding force between the solid particles is also insufficient. When the bonding force is insufficient, due to the charge and discharge of the all-solid-state secondary battery (release and absorption of metal ions of the active material), the bonding between the solid particles is poor (generating gaps), and it is inevitable that the battery performance (such as cycle characteristics) decreases.
[0009] In order to solve this problem, as shown in patent document 1, solid particles and polymer binders are being studied. However, since polymer binders generally do not have ion conductivity, the resistance of the all-solid-state secondary battery using polymer binders is further increased together with the high interface resistance of the above-mentioned solid particles, thereby causing a reduction in battery performance (battery voltage). In particular, in order to enhance the cohesive force of solid particles, the amount used is increased, and, as shown in patent document 1, when polymer binders are continuously present between solid particles, the increase in resistance becomes significant. In this way, when solid particles and polymer binders are used together, the cohesiveness enhancement of solid particles and the reduction of interface resistance (suppressing the rise of interface resistance) are a trade-off relationship, and it is hoped to overcome this point.
[0010] In recent years, the research and development of high performance and practical application of electric vehicles has been progressing rapidly, and the requirements for battery performance required for all-solid-state secondary batteries are getting higher and higher. In order to meet this requirement, it is necessary to develop a constituent layer forming material that has both the cohesiveness enhancement of solid particles and the reduction of interface resistance at a higher level. However, the solid electrolyte composition described in patent document 1 does not describe this viewpoint.
[0011] The subject of the present invention is to provide an inorganic solid electrolyte composition, which can realize a constituent layer that suppresses the increase of interface resistance while making solid particles firmly bonded to each other by being used as a constituent layer forming material of an all-solid-state secondary battery. In addition, the subject of the present invention is to provide a sheet material for an all-solid-state secondary battery and an all-solid-state secondary battery using the inorganic solid electrolyte composition, and a method for manufacturing the sheet material for an all-solid-state secondary battery and the all-solid-state secondary battery.
[0012] Means for solving technical problems
[0013] As a result of various studies on the bonding state of polymer binders used in combination with inorganic solid electrolytes, the inventors found that the crystallinity of the polymer forming the polymer binder, which has not been paid attention to, can improve the contact state (contact area) and bonding force between the solid particles in a well-balanced manner when the solid particles are bonded to each other. According to this view, the results of further research found that on the basis of using two or more polymer binders different from each other for inorganic solid electrolytes, at least one polymer binder is formed by a crystalline polymer with a crystallization temperature of more than 60°C, and the inorganic solid electrolyte composition containing other polymer binders is set as a particle-shaped material for the constituent layer of the all-solid-state secondary battery, so that the solid particles can be firmly bonded to each other while fully ensuring the interface contact state between the solid particles. In addition, it was found that by using the constituent layer formed by the inorganic solid electrolyte composition as a sheet for all-solid-state secondary batteries or a constituent layer of all-solid-state secondary batteries, for all-solid-state secondary batteries, it is possible to achieve low resistance of battery resistance and further improve battery performance (cycle characteristics). The present invention has been further repeatedly studied based on these insights, thereby completing the present invention.
[0014] That is, the above-mentioned problems are solved by the following means.
[0015] <1> An inorganic solid electrolyte composition comprising an inorganic solid electrolyte having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table and a polymer binder, wherein:
[0016] The polymer binder comprises at least two different polymer binders A and B,
[0017] The polymer binder A is in a particle form, and the polymer binder B is a polymer binder composed of a polymer having a crystallization temperature of 60° C. or higher.
[0018] <2> according to <1> The inorganic solid electrolyte composition also contains a dispersion medium.
[0019] <3> according to <2> The inorganic solid electrolyte composition, wherein the dispersion medium is a non-polar dispersion medium.
[0020] <4> according to <3> The inorganic solid electrolyte composition, wherein:
[0021] The solubility of the polymer binder B in the nonpolar dispersion medium is 2% by mass or more.
[0022] <5> according to <3> or <4> The inorganic solid electrolyte composition, wherein:
[0023] The solubility of the polymer binder A in the nonpolar dispersion medium is 1% by mass or less.
[0024] <6> according to <1> to <5> Any one of the inorganic solid electrolyte-containing compositions, wherein
[0025] The polymer forming the polymer binder B is a fluorine-based polymer, a hydrocarbon-based polymer, a polyurethane, or a (meth)acrylic polymer.
[0026] <7> according to <1> to <6> Any one of the inorganic solid electrolyte-containing compositions, wherein
[0027] The polymer forming the polymer binder A is a polyurethane or a (meth)acrylic polymer.
[0028] <8> according to <1> to <7> The inorganic solid electrolyte-containing composition described above further contains an active material.
[0029] <9> according to <8> The inorganic solid electrolyte composition, wherein:
[0030] The polymer binder B has a peel strength of 0.1 N / mm or more with respect to the current collector.
[0031] <10> A sheet material for all-solid-state secondary battery, comprising the above <1> to <9> A layer comprising the inorganic solid electrolyte composition described in any one of the above.
[0032] <11> according to <10> The all-solid-state secondary battery sheet, wherein:
[0033] The layer composed of the inorganic solid electrolyte composition is a product obtained by heating and drying the inorganic solid electrolyte composition at a temperature not lower than the crystallization temperature of the polymer binder B.
[0034] <12> according to <10> or <11> The all-solid-state secondary battery sheet, wherein:
[0035] The layer composed of the inorganic solid electrolyte composition is 10 μm 2 The cross-sectional area includes more than 30 particulate regions derived from the polymer binder.
[0036] <13> An all-solid-state secondary battery comprises a positive electrode active material layer, a solid electrolyte layer and a negative electrode active material layer in sequence, wherein:
[0037] At least one of the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer is <1> to <9> A layer comprising the inorganic solid electrolyte composition described in any one of the above.
[0038] <14> A method for manufacturing a sheet material for an all-solid-state secondary battery, comprising using the above <1> to <9> A step of forming a film containing the inorganic solid electrolyte composition described in any one of the above.
[0039] <15> according to <14> The method for manufacturing a sheet material for an all-solid-state secondary battery, wherein:
[0040] The inorganic solid electrolyte-containing composition is heated at a temperature equal to or higher than the crystallization temperature of the polymer binder B.
[0041] <16> A method for manufacturing an all-solid-state secondary battery, comprising the above <14> or <15> The invention discloses a method for manufacturing the sheet material for the all-solid-state secondary battery.
[0042] Effects of the Invention
[0043] The inorganic solid electrolyte composition of the present invention is used as a constituent layer forming material of an all-solid-state secondary battery, and it is possible to achieve a constituent layer in which solid particles are firmly bonded to each other while suppressing the rise of interface resistance. In addition, the all-solid-state secondary battery sheet of the present invention is used as a constituent layer of an all-solid-state secondary battery, and it is possible to achieve an all-solid-state secondary battery showing low resistance of battery resistance and excellent battery performance (cycle characteristics). In addition, the all-solid-state secondary battery of the present invention shows low resistance and excellent battery performance (cycle characteristics).
[0044] Each method for producing the sheet for an all-solid-state secondary battery and the all-solid-state secondary battery of the present invention can produce the sheet for an all-solid-state secondary battery and the all-solid-state secondary battery that exhibit the above-mentioned excellent characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a longitudinal sectional view schematically showing an all-solid-state secondary battery according to a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0046] In the present specification, a numerical range represented by "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0047] In this specification, the term "compound" (for example, when the term "compound" is appended to the end) includes not only the compound itself but also its salts and ions, and includes derivatives in which a part is changed by introducing a substituent, etc., within the range that does not impair the effects of the present invention.
[0048] In the present invention, (meth)acrylic acid refers to one or both of acrylic acid and methacrylic acid. The same applies to (meth)acrylate.
[0049] In this specification, about the substituent, linking group etc. (hereinafter referred to as substituent etc.) that are not clearly recorded to be substituted or unsubstituted, it means that the group may also have a suitable substituent. Therefore, in this specification, even if it is simply recorded as a YYY group, the YYY group further includes a mode with a substituent in addition to including a mode without a substituent. This is also the same for compounds that are not clearly recorded to be substituted or unsubstituted. As a preferred substituent, for example, the substituent Z described later can be cited.
[0050] In this specification, when there are multiple substituents etc. represented by specific symbols or when multiple substituents etc. are specified simultaneously or selectively, it means that each substituent etc. may be the same or different from each other. Moreover, even if there is no special description, when multiple substituents etc. are adjacent, it means that these may be linked or fused to each other to form a ring.
[0051] [Inorganic solid electrolyte composition]
[0052] The inorganic solid electrolyte-containing composition of the present invention contains an inorganic solid electrolyte having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table and a polymer binder.
[0053] The inorganic solid electrolyte-containing composition of the present invention comprises at least two different polymer binders A and B. The polymer binder A is a particulate polymer binder, and the polymer binder B is a polymer binder composed of a polymer having a crystallization temperature of 60° C. or higher.
[0054] In the present invention, polymer binder A and polymer binder B are different from each other, which means that the chemical structures or properties of the two polymer binders are different, wherein one polymer binder is in a particulate form in the inorganic solid electrolyte composition, and the other polymer binder is composed of a crystalline polymer. For example, the combination of polymer binders A and B includes a combination of particulate polymer binders composed of crystalline polymers of different polymer types or compositions.
[0055] The polymer binder contained in the inorganic solid electrolyte composition of the present invention acts as a binder that firmly bonds solid particles to each other while suppressing the increase of interface resistance, and bonds the collector and solid particles according to the situation in the solid electrolyte layer formed by at least the inorganic solid electrolyte composition. In addition, the polymer binder may or may not have the function of bonding solid particles such as inorganic solid electrolytes (in addition, active materials and conductive additives that can coexist) to each other (for example, inorganic solid electrolytes to each other, inorganic solid electrolytes and active materials, active materials to each other) in the inorganic solid electrolyte composition, and may also have the function of being dispersed in a dispersion medium according to the situation.
[0056] The inorganic solid electrolyte composition of the present invention can form a constituent layer that suppresses the increase of interface resistance and firmly bonds solid particles to each other. The all-solid-state secondary battery sheet and all-solid-state secondary battery having such a constituent layer can achieve both low resistance of the battery and cycle characteristics at a higher level.
[0057] The detailed reasons are not clear, but it is considered as follows. That is, it is believed that the polymer binder B formed by a crystalline polymer with a crystallization temperature of 60°C or more can bind the solid particles to each other by causing the crystalline component to interact with the solid particles (for example, van der Waals interaction). On the other hand, the non-crystalline component (dissolved component) possessed by the polymer forming the polymer binder B becomes the main cause of the increase in interface resistance when the surface of the solid particles is coated. However, in the present invention, it is believed that by combining a particulate polymer binder with a polymer binder B (replacing a part of the polymer binder B with a polymer binder A), the surface coating amount of the solid particles based on the two polymer binders can be reduced without damaging the firm bonding between the solid particles.
[0058] It is considered that the effects of these two polymer binders can strongly bind the solid particles to each other while suppressing an increase in interface resistance, and that both low resistance and cycle characteristics of the all-solid-state secondary battery can be achieved at a higher level.
[0059] It can be considered that, in particular, when the crystalline components of the polymer binder B used in combination with the polymer binder A are temporarily melted and then recrystallized during the formation process of the constituent layer, the solid particles can be more firmly bonded to each other, and as the recrystallization proceeds, the volume of the polymer binder coating the surface of the solid particles shrinks and the coating amount decreases, which can ensure the interface contact between the solid particles. Thus, a balance can be achieved between the firm bonding force between the solid particles and the suppression of the rise in interface resistance.
[0060] The inorganic solid electrolyte composition of the present invention can be preferably used as a sheet for all-solid-state secondary batteries, an electrode sheet for all-solid-state secondary batteries, or a solid electrolyte layer or active material layer forming material (constituent layer forming material) of an all-solid-state secondary battery. In particular, it can be preferably used as a negative electrode sheet or a negative electrode active material layer forming material for all-solid-state secondary batteries containing a negative electrode active material with large expansion and contraction caused by charge and discharge, and in this way, a high active material capacity is shown, but low resistance and high cycle characteristics can also be achieved.
[0061] The inorganic solid electrolyte composition of the present invention is preferably a non-aqueous composition. In the present invention, the non-aqueous composition, in addition to including a mode that does not contain water, also includes a mode in which the water content (also referred to as water content) is preferably 500ppm or less. In the non-aqueous composition, the water content is more preferably 200ppm or less, further preferably 100ppm or less, and particularly preferably 50ppm or less. If the inorganic solid electrolyte composition is a non-aqueous composition, the degradation of the inorganic solid electrolyte can be suppressed. The water content represents the amount of water contained in the inorganic solid electrolyte composition (to the mass ratio of the inorganic solid electrolyte composition), specifically, it is set to a value obtained by filtering with a 0.02μm membrane filter and measuring by Karl Fischer titration.
[0062] The inorganic solid electrolyte-containing composition of the present invention also includes an embodiment in which it contains an active material, a conductive auxiliary agent, etc. in addition to the inorganic solid electrolyte (a composition of this embodiment is referred to as an electrode composition).
[0063] Hereinafter, components contained in and components that may be contained in the inorganic solid electrolyte composition of the present invention will be described.
[0064] <Inorganic solid electrolyte>
[0065] The inorganic solid electrolyte-containing composition of the present invention contains an inorganic solid electrolyte.
[0066] In the present invention, an inorganic solid electrolyte refers to an inorganic solid electrolyte, and a solid electrolyte refers to a solid electrolyte that enables ions to move inside it. Considering that an organic substance that is not included as the main ion conductive material is not included, it is clearly distinguished from an organic solid electrolyte (a polymer electrolyte represented by polyethylene oxide (PEO), etc., an organic electrolyte salt represented by lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), etc.). In addition, since the inorganic solid electrolyte is solid in a stable state, it is usually not dissociated or freed into cations and anions. At this point, it is clearly distinguished from an inorganic electrolyte salt (LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI), LiCl, etc.) that is dissociated or freed into cations and anions in an electrolyte or a polymer. As long as the inorganic solid electrolyte has the ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, it is not particularly limited and usually does not have electronic conductivity. When the all-solid-state secondary battery of the present invention is a lithium-ion battery, the inorganic solid electrolyte preferably has ion conductivity of lithium ions.
[0067] The above-mentioned inorganic solid electrolyte can be appropriately selected from solid electrolyte materials commonly used in all-solid-state secondary batteries. For example, as inorganic solid electrolytes, (i) sulfide-based inorganic solid electrolytes, (ii) oxide-based inorganic solid electrolytes, (iii) halide-based inorganic solid electrolytes, and (iv) hydride-based solid electrolytes can be listed. From the perspective of being able to form a better interface between the active material and the inorganic solid electrolyte, sulfide-based inorganic solid electrolytes are preferred.
[0068] (i) Sulfide-based inorganic solid electrolytes
[0069] The sulfide-based inorganic solid electrolyte preferably contains a sulfur atom and has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table and is an electronically insulating compound. The sulfide-based inorganic solid electrolyte preferably contains at least Li, S, and P as elements and has lithium ion conductivity, but may contain elements other than Li, S, and P depending on the purpose or circumstances.
[0070] Examples of the sulfide-based inorganic solid electrolyte include lithium ion conductive inorganic solid electrolytes satisfying a composition represented by the following formula (S1).
[0071] L a1 M b1 P c1 S d1 A e1 (S1)
[0072] In the formula, L represents an element selected from Li, Na and K, preferably Li. M represents an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al and Ge. A represents an element selected from I, Br, Cl and F. a1~e1 represent the composition ratio of each element, and a1:b1:c1:d1:e1 satisfies 1~12:0~5:1:2~12:0~10. a1 is preferably 1~9, and more preferably 1.5~7.5. b1 is preferably 0~3, and more preferably 0~1. d1 is preferably 2.5~10, and more preferably 3.0~8.5. e1 is preferably 0~5, and more preferably 0~3.
[0073] As described below, the composition ratio of each element can be controlled by adjusting the blending amount of the raw material compound when producing the sulfide-based inorganic solid electrolyte.
[0074] The sulfide-based inorganic solid electrolyte may be amorphous (glass), crystallized (glass ceramic), or only partially crystallized. For example, Li-PS-based glass containing Li, P, and S or Li-PS-based glass ceramic containing Li, P, and S may be used.
[0075] Sulfide-based inorganic solid electrolytes can be manufactured by reacting at least two or more raw materials, for example, lithium sulfide (Li2S), phosphorus sulfide (for example, phosphorus pentasulfide (P2S5)), elemental phosphorus, elemental sulfur, sodium sulfide, hydrogen sulfide, lithium halide (for example, LiI, LiBr, LiCl) and sulfides of the elements represented by the above M (for example, SiS2, SnS, GeS2).
[0076] The ratio of Li2S to P2S5 in the Li-PS glass and Li-PS glass ceramics is preferably 60:40 to 90:10, and more preferably 68:32 to 78:22, in terms of the molar ratio of Li2S:P2S5. By setting the ratio of Li2S to P2S5 to this range, the lithium ion conductivity can be improved. Specifically, the lithium ion conductivity can be preferably set to 1×10 -4 S / cm or more, more preferably 1×10 -3 S / cm or more. Although there is no specific upper limit, it is actually 1×10 -1 S / cm or less.
[0077] As specific examples of sulfide-based inorganic solid electrolytes, the combination of raw materials is shown below. For example, Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SiS2-LiCl, Li2S-P2S5-SnS, Li2S-P2S5-Al2S 3. Li2S-GeS2, Li2S-GeS2-ZnS, Li2S-Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, L i2S-Al2S3, Li2S-SiS2-Al2S3, Li2S-SiS2-P2S5, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li 10 GeP2S 12etc. Among them, the mixing ratio of each raw material is not limited. As a method for synthesizing a sulfide-based inorganic solid electrolyte material using such a raw material composition, for example, an amorphization method can be cited. As an amorphization method, for example, a mechanical polishing method, a solution method, and a melt quenching method can be cited. It is possible to perform treatment at room temperature, thereby simplifying the manufacturing process.
[0078] (ii) Oxide-based inorganic solid electrolytes
[0079] The oxide-based inorganic solid electrolyte is preferably a compound that contains oxygen atoms, has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and has electron insulating properties.
[0080] The ion conductivity of the oxide-based inorganic solid electrolyte is preferably 1×10 -6 S / cm or more, more preferably 5×10 -6 S / cm or more, particularly preferably 1×10 -5 S / cm or more. Although there is no specific upper limit, it is actually 1×10 -1 S / cm or less.
[0081] As specific examples of compounds, for example, Li xa La ya TiO3〔xa satisfies 0.3≤xa≤0.7, ya satisfies 0.3≤ya≤0.7.〕(LLT); Li xb La yb Zr zb M bb mb O nb (M bb is one or more elements selected from the group consisting of Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In and Sn. xb satisfies 5≤xb≤10, yb satisfies 1≤yb≤4, zb satisfies 1≤zb≤4, mb satisfies 0≤mb≤2, and nb satisfies 5≤nb≤20. ); Li xc B yc M cc zc O nc (M cc is one or more elements selected from C, S, Al, Si, Ga, Ge, In and Sn. xc satisfies 0<xc≤5, yc satisfies 0<yc≤1, zc satisfies 0<zc≤1, and nc satisfies 0<nc≤6. ); Li xd (Al, Ga) yd (Ti, Ge) zd Si ad P md O nd(xd satisfies 1≤xd≤3, yd satisfies 0≤yd≤1, zd satisfies 0≤zd≤2, ad satisfies 0≤ad≤1, md satisfies 1≤md≤7, and nd satisfies 3≤nd≤13.) (3-2xe) M ee xe D ee O(xe represents a number greater than or equal to 0 and less than or equal to 0.1, M ee Represents a divalent metal atom. ee represents a halogen atom or a combination of two or more halogen atoms. );Li xf Si yf O zf (xf satisfies 1≤xf≤5, yf satisfies 0<yf≤3, zf satisfies 1≤zf≤10.) xg S yg O zg (xg satisfies 1≤xg≤3, yg satisfies 0<yg≤2, zg satisfies 1≤zg≤10.);Li3BO3;Li3BO3-Li2SO4;Li2O-B2O3-P2O5;Li2O-SiO2;Li6BaLa2Ta2O 12 ;Li3PO (4-3 / 2w) N w (w satisfies w<1); Li with LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zn 0.25 GeO4; La with perovskite crystal structure 0.55 Li 0.35 TiO3; LiTi2P3O with NASICON (Natrium superionic conductor) type crystal structure 12 ;Li 1+xh+yh (Al, Ga) xh (Ti, Ge) 2-xh Si yh P 3-yh O 12 (xh satisfies 0≤xh≤1, yh satisfies 0≤yh≤1.); Li7La3Zr2O with garnet crystal structure 12 (LLZ) etc.
[0082] Furthermore, phosphorus compounds containing Li, P, and O are also preferred. Examples thereof include lithium phosphate (Li3PO4); LiPON in which a portion of oxygen in lithium phosphate is substituted with nitrogen; and LiPOD. 1 (D 1Preferably, it is one or more elements selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt and Au. ) etc.
[0083] In addition, LiA can also be preferably used 1 ON(A 1 It is one or more elements selected from Si, B, Ge, Al, C and Ga. ) etc.
[0084] (iii) Halide-based inorganic solid electrolytes
[0085] The halide-based inorganic solid electrolyte is preferably a compound containing a halogen atom, having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and having electron insulating properties.
[0086] There are no particular restrictions on the halide-based inorganic solid electrolyte, and examples thereof include LiCl, LiBr, LiI, and compounds such as Li3YBr6 and Li3YCl6 described in ADVANCED MATERIALS, 2018, 30, 1803075. Among them, Li3YBr6 and Li3YCl6 are preferred.
[0087] (iv) Hydride-based inorganic solid electrolytes
[0088] The hydride-based inorganic solid electrolyte is preferably a compound that contains hydrogen atoms, has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and has electron insulating properties.
[0089] The hydride-based inorganic solid electrolyte is not particularly limited, and examples thereof include LiBH4, Li4(BH4)3I, and 3LiBH4-LiCl.
[0090] The inorganic solid electrolyte is preferably in the form of particles. In this case, the particle size (volume average particle size) of the inorganic solid electrolyte is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.1 μm or more. The upper limit is preferably 100 μm or less, more preferably 50 μm or less.
[0091] The particle size of the inorganic solid electrolyte is determined by the following steps. In a 20 mL sample bottle, a dispersion of 1% by mass of inorganic solid electrolyte particles is prepared by diluting with water (butyl butyrate in the case of a substance unstable to water). The diluted dispersion sample is irradiated with 1 kHz of ultrasound for 10 minutes and then used immediately in the test. Using the dispersion sample, a laser diffraction / scattering particle size distribution measuring device LA-920 (trade name, manufactured by HORIBA, Ltd.) is used and 50 data collections are performed at a temperature of 25°C using a quartz cell for measurement to obtain the volume average particle size. For other detailed conditions, refer to the description in JIS Z8828:2013 "Particle Size Analysis-Dynamic Light Scattering Method" as needed. Five samples are prepared for each level and their average value is adopted.
[0092] The inorganic solid electrolyte may contain one kind or two or more kinds.
[0093] When a solid electrolyte layer is formed, the solid electrolyte layer has a surface area (cm 2 The mass (mg) (weight per unit area) of the inorganic solid electrolyte is not particularly limited. It can be appropriately determined according to the designed battery capacity, for example, it can be set to 1 to 100 mg / cm 2 .
[0094] When the inorganic solid electrolyte-containing composition contains an active material described later, the total amount of the active material and the inorganic solid electrolyte is preferably within the above range regarding the weight per unit area of the inorganic solid electrolyte.
[0095] The content of the inorganic solid electrolyte in the inorganic solid electrolyte composition is not particularly limited. From the perspective of reducing the interface resistance and the adhesiveness, the solid content is preferably 50% by mass or more, more preferably 70% by mass or more, and particularly preferably 90% by mass or more in 100% by mass of the solid component. As the upper limit, from the same perspective, it is preferably 99.9% by mass or less, more preferably 99.5% by mass or less, and particularly preferably 99% by mass or less.
[0096] However, when the inorganic solid electrolyte-containing composition contains an active material described below, the content of the inorganic solid electrolyte in the inorganic solid electrolyte-containing composition is preferably a total content of the active material and the inorganic solid electrolyte within the above range.
[0097] In this specification, solid content refers to components that do not disappear when the inorganic solid electrolyte composition is dried at 150° C. for 6 hours under a nitrogen atmosphere at a pressure of 1 mmHg. Typically, it refers to components other than the dispersion medium described below.
[0098] <Polymer Binder>
[0099] The inorganic solid electrolyte-containing composition of the present invention may contain at least a particulate polymer binder A and a polymer binder B composed of a polymer having a crystallization temperature of 60° C. or higher, and may also contain other polymer binders. In the present invention, the polymer binder A, the polymer binder B, and the other polymer binders may each be one or more.
[0100] The inorganic solid electrolyte-containing composition of the present invention may contain two or more polymer binders, and usually, preferably 2 to 4 polymer binders, and more preferably two polymer binders, one polymer binder A and one polymer binder B.
[0101] (Polymer Binder A)
[0102] The polymer binder A is preferably contained in the inorganic solid electrolyte-containing composition in a particle state, and is also present in a solid state (maintaining a particle state) in the constituent layer described later.
[0103] In the inorganic solid electrolyte-containing composition, by using the particulate polymer binder A and the polymer binder B in combination, the interface resistance between the solid particles can be reduced without impairing the strong bonding between the solid particles.
[0104] In the inorganic solid electrolyte composition, particulate means that the particles are present (preferably dispersed) as particles that are insoluble in the dispersion medium preferably contained in the inorganic solid electrolyte composition (not dissolved in the dispersion medium and in a solid state). In the present invention, the polymer binder that is present in a solid state in the inorganic solid electrolyte composition (dispersion medium) is referred to as a particulate polymer binder.
[0105] In the present invention, insoluble in the dispersion medium means that the solubility in the non-polar dispersion medium calculated by the method described in the examples is 1% by mass or less. On the other hand, soluble in the dispersion medium means that the solubility in the non-polar dispersion medium calculated by the method described in the examples exceeds 1% by mass, preferably 2% by mass or more.
[0106] When the polymer binder is a particulate polymer binder, its shape is not particularly limited, and can be flat, amorphous, etc., preferably spherical or granular. The average particle size of the particulate polymer binder is not particularly limited, preferably 5000nm or less, more preferably 1500nm or less, and more preferably 1000nm or less. The lower limit is more than 1nm, preferably more than 5nm, more preferably more than 10nm, and more preferably more than 100nm. The average particle size of the particulate polymer binder can be measured in the same manner as the average particle size of the above-mentioned inorganic solid electrolyte.
[0107] In addition, the particle size of the particulate polymer binder in the constituent layer of the all-solid-state secondary battery can be measured, for example, by disassembling the battery and peeling off the constituent layer containing the particulate polymer binder, measuring the constituent layer, and removing the measured value of the particle size of particles other than the particulate polymer binder that has been measured in advance.
[0108] The particle size of the particulate polymer binder can be adjusted by, for example, the type of dispersion medium, the content of constituent components in the polymer, and the like.
[0109] The polymer binder A preferably has a high adsorption rate to the inorganic solid electrolyte from the viewpoint of being able to enhance the bonding force of the polymer binder B and achieve a strong bond between the solid particles. For example, the adsorption rate of the polymer binder A relative to the inorganic solid electrolyte is not particularly limited, but from the viewpoint of being able to achieve a strong bond between the solid particles, it is 15% or more, preferably 25% or more, more preferably 50% or more, and further preferably 55% or more. On the other hand, the upper limit of the adsorption rate is not particularly limited, and is actually 99.9%. From the viewpoint of dispersibility, it is preferably 90% or less.
[0110] In the present invention, the adsorption rate of the polymer binder is an index indicating the degree of adsorption of the polymer binder relative to the inorganic solid electrolyte contained in the inorganic solid electrolyte composition containing the polymer binder in the dispersion medium. Here, the adsorption of the polymer binder relative to the inorganic solid electrolyte includes not only physical adsorption, but also chemical adsorption (adsorption by forming chemical bonds, adsorption by electron transfer, etc.). In addition, the dispersion medium usually uses butyl butyrate, which may be different from the dispersion medium contained in the inorganic solid electrolyte composition containing the polymer binder. Therefore, when the inorganic solid electrolyte composition containing multiple inorganic solid electrolytes, it becomes the adsorption rate of the inorganic solid electrolyte having the same composition (type and content) as the inorganic solid electrolyte in the inorganic solid electrolyte composition. When using multiple polymer binders, it is also set to the adsorption rate of multiple polymer binders.
[0111] In the present invention, the adsorption rate of the polymer binder is set to a value calculated by the method described in Examples.
[0112] In the present invention, the adsorption rate of the inorganic solid electrolyte can be appropriately set by the type of polymer forming the polymer binder (the structure and composition of the polymer chain), the type or content of the functional groups possessed by the polymer, the form of the polymer binder (particulate polymer binder or dissolved polymer binder), the presence or absence and content of crystalline components, etc.
[0113] When the inorganic solid electrolyte composition of the present invention contains the active material described later (when the active material layer is formed by the inorganic solid electrolyte composition), the adsorption rate of the polymer binder A to the active material is not particularly limited. From the perspective of further improving the bonding property, it is preferably 10% or more, more preferably 20 to 99.9%, and further preferably 30 to 99%. In the present invention, the adsorption rate of the polymer binder to the active material is an index indicating the degree of adsorption of the polymer binder in the dispersion medium relative to the active material contained in the inorganic solid electrolyte composition using the polymer binder. Here, the adsorption of the polymer binder to the active material includes not only physical adsorption, but also chemical adsorption (adsorption by forming a chemical bond, adsorption by electron donation, etc.). In addition, butyl butyrate is usually used as the dispersion medium, and it may be different from the dispersion medium contained in the inorganic solid electrolyte composition using the polymer binder. Therefore, when the inorganic solid electrolyte composition contains multiple active materials, for the case of using multiple polymer binders, the adsorption rate of the above-mentioned polymer binder to the inorganic solid electrolyte is the same. In the present invention, the adsorption rate of the polymer binder to the active material is set to the value calculated by the method described in the embodiment. In the present invention, the adsorption rate to the active material can be appropriately set similarly to the adsorption rate to the inorganic solid electrolyte.
[0114] The polymer forming the polymer binder A may be a crystalline polymer or a non-crystalline polymer, and is preferably a non-crystalline polymer from the viewpoint of high adsorption rate and strong adhesion. In the present invention, the details are described later, and a crystalline polymer refers to a polymer having a crystallization temperature, and a non-crystalline polymer refers to a polymer having no crystallization temperature (no crystallization peak is observed in the thermal analysis described later). The control of crystalline polymers and non-crystalline polymers is also described later.
[0115] In the present invention, it is preferred that the polymer forming the polymer binder A used in combination with the polymer binder B does not melt or undergo glass transition at a temperature lower than the crystallization temperature of the polymer forming the polymer binder B. Thus, a predetermined particle shape is maintained even in the constituent layer, and the enhancement of adhesion and the reduction of interface resistance by the polymer binder B can be effectively enhanced.
[0116] The SP value of the polymer forming the polymer binder A is not particularly limited, but is preferably 10 to 23, more preferably 10 to 22, and further preferably 11 to 21 from the viewpoint of compatibility with the inorganic solid electrolyte composition and improvement of dispersibility when containing a dispersion medium. The SP value of the polymer can be adjusted according to the type and composition (type and content of constituent components) of the polymer. The method for measuring the SP value will be described later.
[0117] The peel strength of the polymer binder A relative to the collector is not particularly limited and can be appropriately set. For example, it can be set to the same range as the peel strength of the polymer binder B to the collector described later. Thus, when the active material layer is formed by the inorganic solid electrolyte composition of the present invention, the adhesion between the collector and the active material layer can be improved.
[0118] The content of the polymer binder A in the inorganic solid electrolyte composition is not particularly limited, but is preferably 0.1 to 5.0% by mass, more preferably 0.2 to 3.0% by mass, and further preferably 0.3 to 1.0% by mass in 100% by mass of the solid content from the viewpoint of enhancing adhesion and reducing interface resistance. In addition, the content of the polymer binder A can be appropriately set within the above range, but the lower limit thereof is preferably a content that is insoluble in the inorganic solid electrolyte composition (can maintain a particle shape) in consideration of the solubility of the polymer binder A.
[0119] In the inorganic solid electrolyte composition, the content of polymer binder A may be lower than the content of polymer binder B described later, but is preferably the same or higher. Thus, it is possible to improve the adhesion enhancement and the reduction of interface resistance. The difference in the content of polymer binder A and polymer binder B (the content of polymer binder A - the content of polymer binder B) is not particularly limited, for example, it can be set to -5.0 to 5.0% by mass, preferably 0.0% by mass or more, more preferably 0.0 to 4.0% by mass, and can also be set to 0.2 to 2.0% by mass. In addition, the ratio of the content of polymer binder A to that of polymer binder B (the content of polymer binder A / the content of polymer binder B) is not particularly limited, for example, it is preferably 0.5 to 30, and more preferably 1 to 10.
[0120] (Polymer Binder)
[0121] The polymer binder B is composed of a polymer having a crystallization temperature of 60° C. or higher. In the present invention, the polymer binder being composed of a polymer means that the polymer binder is composed of a polymer, and includes a form of being composed of a mixture containing a polymer, in addition to a form of being composed of only a polymer. Therefore, the polymer binder B also has a crystallization temperature of 60° C. or higher.
[0122] The crystalline polymer forming the polymer binder B generally has a crystalline component and a non-crystalline component. In the present invention, the crystalline component refers to a component having a crystallization temperature in the thermal analysis described below, and the non-crystalline component refers to a component having no crystallization temperature.
[0123] The method of imparting crystallinity to the polymer forming the polymer binder B is not unique depending on the type of polymer and the like.
[0124] For example, regarding chain polymerization polymers, the setting of the primary structure of the polymer and the control of the secondary structure can be cited. Specifically, if the regularity of the primary structure of the polymer is improved, crystallinity is easily found, for example, the crystallinity can be expressed by the control of the stereoisomerism (stereoregularity) such as isotactic and syndiotactic of the polymerization mode of block polymers, alternating polymers, and the expression of folded structures.
[0125] The stepwise polymerization type polymer can be exemplified by setting the primary structure of the polymer and controlling the secondary structure. Specifically, crystallinity can be expressed by, for example, selecting a functional group.
[0126] In the present invention, the degree of adjustment in each method of imparting the above-mentioned crystallinity is not particularly limited as long as it can be confirmed that the crystallization temperature is 60° C. or above, and can be appropriately determined. For example, in the case of a block polymer, the degree of polymerization or mass ratio of each block, and even the type and content of the constituent components constituting each block can be cited, which can be appropriately determined according to the crystallization temperature.
[0127] Whether a polymer has crystallinity can be confirmed by the presence of a crystallization peak in the following method for measuring the crystallization temperature.
[0128] The crystallization temperature of the crystalline polymer is above 60°C. By forming the polymer binder B from a polymer having a crystallization temperature of above 60°C, the crystalline component easily interacts with the solid particles, and the solid particles can be bonded to each other without damaging the interfacial contact state between the solid particles. In particular, when the crystalline component is melted in the drying process, it becomes a crystalline state at room temperature after melting, so that the interfacial contact state between the solid particles can be ensured while firmly bonding. From the perspective of being able to take into account both the reduction of interface resistance and the enhancement of adhesion at a high level and with good balance, the crystallization temperature is preferably above 70°C, more preferably above 75°C, and further preferably above 80°C. On the other hand, the upper limit of the crystallization temperature is not particularly limited. From the perspective of promoting melting during drying, it is actually below 150°C, preferably below 140°C, more preferably below 135°C, and further preferably below 130°C.
[0129] The crystallization temperature of a polymer can be determined by thermal analysis. Specifically, a dried sample of the polymer is used as the measurement object, and the measurement is performed under the following conditions using a differential scanning calorimeter: X-DSC7000 (trade name, manufactured by SII Nano Technology Inc.). During the measurement, the same sample is measured twice, and the second measurement result is used.
[0130] Ambient gas in the measurement room: Nitrogen (50mL / min)
[0131] Heating rate: 5℃ / min
[0132] Measurement starting temperature: -50℃
[0133] Measurement end temperature: 350℃
[0134] Sample pan: Aluminum pan
[0135] The mass of the sample to be measured: 5 mg
[0136] Calculation of crystallization temperature: The crystallization temperature was calculated by rounding off the decimal point of the endothermic peak temperature of the DSC chart.
[0137] In addition, when using an all-solid-state secondary battery, for example, it can be carried out in the following manner, that is, the all-solid-state secondary battery is decomposed and the active material layer or solid electrolyte layer is placed in water to disperse its materials, and then filtered to collect the remaining solids, and the crystallization temperature is measured using the above-mentioned measurement method.
[0138] The crystallization temperature is measured with respect to the polymer, but generally, the same value can be obtained even when the polymer binder is measured, so the crystallization temperature of the polymer binder can be used instead. The polymer binder B in the constituent layer can be recovered from the constituent layer and measured.
[0139] The crystallization temperature of the polymer can be appropriately set depending on the degree of adjustment of the method for imparting crystallinity, the type of polymer (polymer composition), the type or content of functional groups possessed by the polymer, the molecular weight, and the like.
[0140] In the polymer forming the polymer binder B, the content ratio of the crystalline component to the non-crystalline component is not particularly limited as long as the above-mentioned crystallization temperature is satisfied, and can be appropriately set according to the type of polymer, the level of the crystallization temperature, etc. For example, the content ratio of the crystalline component is preferably 30 to 90% by mass, more preferably 40 to 80% by mass, in 100% by mass of the polymer.
[0141] The polymer binder B may be a particulate polymer binder in the inorganic solid electrolyte composition, or may be dissolved in a dispersion medium and exist (the polymer binder that is dissolved and exists is referred to as a dissolving polymer binder). In the present invention, from the viewpoint of the balance between the enhanced cohesiveness of the solid particles and the reduction of the interface resistance, a dissolving polymer binder is preferably used. In particular, when the drying temperature of the constituent layer is set to above the crystallization temperature on the basis of using the polymer binder B as a dissolving polymer binder, the crystalline component of the polymer binder can be temporarily melted and then recrystallized, which is preferred from the viewpoint of being able to more firmly bond while fully ensuring the interface contact between the solid particles.
[0142] In the case of a soluble polymer binder, the solubility in a non-polar dispersion medium (usually butyl butyrate) is not particularly limited as long as it is 2% by mass or more, preferably 3% by mass or more, and more preferably 5% by mass or more. On the other hand, the upper limit of the solubility is not particularly limited, for example, it can be set to 70% by mass, preferably 60% by mass or less.
[0143] The solubility of the polymer binder B can be appropriately set depending on the type of polymer (structure and composition of polymer chains), the type and content of functional groups possessed by the polymer, the presence and content of crystalline components, and molecular weight.
[0144] When the polymer binder B is a particulate polymer binder, the solubility and average particle size can be set in the same manner as those of the polymer binder A described above.
[0145] The adsorption rate of the polymer binder B to the inorganic solid electrolyte is not particularly limited, and is less than 10%, preferably less than 8%, more preferably less than 5%, further preferably less than 4%, and particularly preferably more than 0% and less than 3%. When the polymer binder B shows the above adsorption rate, the aggregation of the inorganic solid electrolyte particles can be prevented, a sheet with uniformly dispersed particles can be obtained during coating and drying, and good battery resistance and cycle characteristics can be achieved.
[0146] When the inorganic solid electrolyte composition of the present invention contains the active material described below, the adsorption rate of the polymer binder B to the active material is not particularly limited, but is preferably 0 to 99.9%, more preferably 2 to 50%, and further preferably 3 to 25% from the viewpoint of adhesion.
[0147] The adsorption rate of the polymer binder, its measurement method and control method are as described in Polymer Binder A.
[0148] The SP value of the polymer forming the polymer binder B is not particularly limited, but is preferably 10 to 23, more preferably 10 to 20, and further preferably 11 to 19 from the viewpoint of compatibility with the inorganic solid electrolyte composition and improvement of dispersibility when a dispersion medium is contained. The SP value of the polymer can be adjusted according to the type and composition (type and content of constituent components) of the polymer, etc.
[0149] The SP value of a polymer is determined as follows.
[0150] In the present invention, the SP value is determined by the Hoy method unless otherwise specified (see HL Hoy JOURNAL OF PAINT TECHNOLOGY Vol. 42, No. 541, 1970, 76-118 and POLYMER HANDBOOK 4 th, Chapter 59, VII 686, Table 5, Table 6 and the following formula in Table 6).
[0151] Although the unit is omitted for the SP value, the unit is MPa. 1 / 2 .
[0152] [Mathematical formula 1]
[0153]
[0154] In the formula, δ t Indicates the SP value. t Molar attraction function (J×cm 3 ) 1 / 2 / mol, and is represented by the following formula. V is the molar volume (cm 3 / mol), and is represented by the following formula. It is represented by the following formula.
[0155] F t =∑n i F t,i V=∑n i V i
[0156]
[0157] In the above formula, F t,i represents the molar attraction function of each structural unit, V i represents the molar volume of each structural unit, Δ (P) T,i Represents the correction value of each structural unit, n i Indicates the number of each structural unit.
[0158] The SP value of the polymer is calculated by the following formula using the constituent components (derived from the raw material compound) and their SP values. In addition, the SP values of the constituent components obtained according to the above literature are converted into SP values (MPa 1 / 2 )(For example, lcal 1 / 2 cm -3 / 2 ≈2.05J 1 / 2 cm -3 / 2 ≈2.05MPa 1 / 2 ) and use.
[0159] SP p 2 =(SP1 2 ×W1)+(SP2 2 ×W2)+……
[0160] In the formula, SP1, SP2, ... represent the SP value of the constituent, and W1, W2, ... represent the mass fraction of the constituent. In the present invention, the mass fraction of a constituent is the mass fraction of the constituent (the raw material compound introduced into the constituent) in the polymer.
[0161] The peel strength of the polymer binder B relative to the collector is not particularly limited and can be appropriately set. In the case of forming an active material layer by the inorganic solid electrolyte composition of the present invention, from the viewpoint of being able to improve the adhesion between the collector and the active material layer, for example, it is preferably 0.1N / mm or more, more preferably 0.2N / mm or more, and further preferably 0.3N / mm or more. The upper limit is not particularly limited, for example, it is actually 10N / mm or less, preferably 2.0N / mm or less. The collector that becomes the object of the above-mentioned peel strength is not particularly limited, as long as it is the collector described later, and copper foil, aluminum foil, stainless steel (SUS) foil, etc. can be cited. The peel strength is independent of the type of the collector and is set to the value calculated in the same manner as the method described in the embodiment (peel strength of aluminum foil or copper foil). In the present invention, the peel strength can be appropriately set in the same manner as the adsorption rate of the inorganic solid electrolyte.
[0162] The content of the polymer binder B in the inorganic solid electrolyte composition is not particularly limited, but is preferably 0.01 to 5% by mass, more preferably 0.05 to 2.0% by mass, and further preferably 0.1 to 1.0% by mass, based on 100% by mass of the solid content, from the viewpoint of enhancing adhesion and reducing interface resistance.
[0163] The total content of polymer binder A and polymer binder B in the inorganic solid electrolyte composition is not particularly limited. From the viewpoint of enhancing adhesion and reducing interface resistance, it is preferably more than 0.5% by mass and less than 3.0% by mass, more preferably 0.6 to 2.5% by mass, and further preferably 0.7 to 2.0% by mass, based on 100% by mass of the solid content.
[0164] In the present invention, the mass ratio of the total mass (total amount) of the inorganic solid electrolyte and the active material to the total mass of the polymer binder A and the polymer binder B [(mass of the inorganic solid electrolyte + mass of the active material) / (mass of the polymer binder A + mass of the polymer binder B)] is preferably in the range of 1,000 to 1. In addition, the ratio is more preferably 500 to 2, and further preferably 100 to 10.
[0165] (Polymer forming polymer binder)
[0166] The polymers forming the polymer binders A and B are not particularly limited as long as they are polymers capable of forming a particulate polymer binder or polymers having a crystallization temperature of 60° C. or higher, and can be appropriately selected from various polymers commonly used in the constituent layers of all-solid-state secondary batteries. As polymers forming each polymer binder, for example, step-polymerization (polycondensation, polyaddition or addition condensation) polymers such as polyurethane, polyurea, polyamide, polyimide, polyester, polyether, polycarbonate, and chain polymerization polymers such as fluorine-based polymers, hydrocarbon-based polymers, vinyl-based polymers, and (meth)acrylic polymers can be cited.
[0167] As polymers of polyurethane, polyurea, polyamide, and polyimide that can be used as step-polymerization polymers, for example, there can be cited polymers having hard segments and soft segments described in Japanese Patent Gazette No. 2015-088480 (polymer binder (B)), polymers for forming binders having at least one constituent component represented by a specific formula described in International Publication No. 2018 / 147051, and polymers described in International Publication Nos. 2018 / 020827 and 2015 / 046313.
[0168] There is no particular limitation on the fluorine-based polymer, and examples thereof include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), a copolymer of polyvinylidene fluoride and hexafluoropropylene (PVdF-HFP), and a copolymer of polyvinylidene fluoride, hexafluoropropylene and tetrafluoroethylene (PVdF-HFP-TFE). In PVdF-HFP, the copolymerization ratio of PVdF to HFP [PVdF:HFP] (mass ratio) is not particularly limited, and from the viewpoint of dispersion stability, it is preferably 9:1 to 5:5, and more preferably 9:1 to 7:3. In PVdF-HFP-TFE, the copolymerization ratio of PVdF, HFP and TFE [PVdF:HFP:TFE] (mass ratio) is not particularly limited, and is preferably 20 to 60:10 to 40:5 to 30.
[0169] The hydrocarbon polymer is not particularly limited, and examples thereof include polyethylene, polypropylene, polyethylene-poly(ethylene-butylene)-polyethylene copolymer, natural rubber, polybutadiene, polyisoprene, polystyrene, polystyrene-butadiene copolymer, polypropylene-polyethylene-polybutylene copolymer (CEBC), styrene-based thermoplastic elastomer, polybutene, acrylonitrile-butadiene copolymer, or hydrogenated (hydrogenated) polymers thereof. The styrene-based thermoplastic elastomer or its hydrogenate is not particularly limited, and examples thereof include styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-isoprene-styrene block copolymer (SIS), hydrogenated SIS, styrene-butadiene-styrene block copolymer (SBS), hydrogenated SBS, styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene rubber (HSBR), etc. In the present invention, the hydrocarbon-based polymer is preferred in that the polymer having no unsaturated group (such as 1,2-butadiene constituent component) bonded to the main chain can suppress the formation of chemical crosslinks.
[0170] As the ethylene polymer, for example, a polymer containing 50 mol% or more of ethylene monomers other than the (meth) acrylic acid compound (M1) can be cited. As the ethylene monomer, vinyl compounds described below can be cited. As the ethylene polymer, specifically, for example, polyvinyl alcohol, polyvinyl acetal, polyvinyl acetate or copolymers containing these can be cited.
[0171] The ethylene polymer preferably has, in addition to the constituents derived from the ethylene monomer, constituents derived from the (meth)acrylic acid compound (M1) that form the (meth)acrylic acid polymer described later, and further constituents (MM) derived from the macromonomer described later. The content of the constituents derived from the ethylene monomer is preferably the same as the content of the constituents derived from the (meth)acrylic acid compound (M1) in the (meth)acrylic acid polymer. The content of the constituents derived from the (meth)acrylic acid compound (M1) is not particularly limited as long as it is less than 50 mol% in the polymer, and is preferably 0 to 40 mol%, more preferably 5 to 35 mol%. The content of the constituent (MM) is preferably the same as that in the (meth)acrylic acid polymer.
[0172] As a (meth) acrylic polymer, it is preferred that the polymer is obtained by (co)polymerizing at least one (meth) acrylic compound (M1) selected from (meth) acrylic compounds, (meth) acrylic ester compounds, (meth) acrylamide compounds and (meth) acrylic nitrile compounds. In addition, it is also preferred that the (meth) acrylic polymer is composed of a copolymer of a (meth) acrylic compound (M1) and other polymerizable compounds (M2). As other polymerizable compounds (M2), there is no particular limitation, and vinyl compounds such as styrene compounds, vinyl naphthalene compounds, vinyl carbazole compounds, allyl compounds, vinyl ether compounds, vinyl ester compounds, and dialkyl itaconic acid compounds can be listed. As a vinyl compound, for example, the "vinyl monomer" described in Japanese Patent Gazette No. 2015-88486 can be listed.
[0173] The content of the other polymerizable compound (M2) in the (meth)acrylic polymer is not particularly limited, and can be, for example, less than 50 mol %.
[0174] Examples of the (meth)acrylic polymer include polymers described in International Publication No. 2016 / 132872, which have a macromonomer having a mass average molecular weight of 1,000 or more incorporated as a side chain component and have at least one of the following functional group (b).
[0175] In addition, examples of polymer binders composed of (meth)acrylic polymers include binder particles (B) having an average particle size of 10 nm to 1,000 nm, which are composed of a polymer incorporating a macromonomer (X) having a number average molecular weight of 1,000 or more as a side chain component, and particularly binders composed of a polymer incorporating a macromonomer containing a self-condensate of 12-hydroxystearic acid, as described in JP-A-2015-88486.
[0176] Among the above polymers, examples of the polymer having a crystallization temperature of 60° C. or higher include hydrocarbon polymers, fluorine polymers, polyamides, and polyphenylene sulfide.
[0177] Examples of the hydrocarbon polymer include block copolymers of polyethylene-block poly(ethylene-butene)-block polyethylene and block copolymers of propylene-ethylene-butene (CEBC).
[0178] Examples of the fluorine-based polymer include polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer (PVDF-HFP-TFE), polytetrafluoroethylene (PTFE), and block copolymers thereof.
[0179] In the present invention, the polymer forming the polymer binder A is preferably a polyurethane, a (meth) acrylic polymer or a fluorine polymer, and more preferably a polyurethane or a (meth) acrylic polymer. The polymer forming the polymer binder B is preferably a fluorine polymer, a hydrocarbon polymer, a polyurethane or a (meth) acrylic polymer, and more preferably a fluorine polymer or a hydrocarbon polymer.
[0180] -Functional Groups-
[0181] The polymer forming the polymer binder preferably has a functional group for improving the wettability or adsorbability on the surface of solid particles such as inorganic solid electrolytes. As such functional groups, groups showing physical interactions such as hydrogen bonds on the surface of solid particles and groups that can form chemical bonds with groups present on the surface of solid particles can be listed, specifically, more preferably having at least one group selected from the following functional group group (I). Wherein, from the viewpoint of more effectively showing wettability or adsorbability on the surface of solid particles, it is preferred not to have more than two groups that can form bonds between functional groups.
[0182] <Functional Group (I)>
[0183] Acidic group, group having basic nitrogen atom, amide group, urea group, carbamate group, alkoxysilyl group, epoxy group, isocyanate group, hydroxyl group or (meth)acryloyloxy group
[0184] The acidic group is not particularly limited, and examples thereof include a carboxylic acid group (-COOH), a sulfonic acid group (sulfonic acid group: -SO3H), a phosphoric acid group (phosphorus group: -OPO(OH)2), a phosphonic acid group, and a phosphinic acid group, and a carboxylic acid group is preferred.
[0185] Examples of the group having a basic nitrogen atom include amino, pyridyl, imino and amidino (-C(=NR)-NR2). The amino group has the same meaning as the amino group of the substituent Z described below, but is preferably an unsubstituted amino group or an alkylamino group. The three Rs of the amidino group each represent a hydrogen atom or a substituent (e.g., a group selected from the substituent Z described below).
[0186] Examples of the ureido group include -NR 15 CONR 16 R 17 (Here, R 15 , R 16 and R 17 represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 or more carbon atoms, or an aralkyl group having 7 or more carbon atoms. ) is a preferred example. As the ureido group, more preferably -NR 15 CONHR 17 (Here, R 15 and R17 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 or more carbon atoms, or an aralkyl group having 7 or more carbon atoms. ), and -NHCONHR is particularly preferred. 17 (Here, R 17 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 or more carbon atoms, or an aralkyl group having 7 or more carbon atoms. ).
[0187] Examples of the carbamate group include -NHCOOR 18 、-NR 19 COOR 20 ,-OCONHR 21 、-OCONR 22 R 23 (Here, R 18 , R 19 , R 20 , R 21 , R 22 and R 23 represents an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 or more carbon atoms, or an aralkyl group having 7 or more carbon atoms. ) and the like, and a group containing at least an imino group and a carbonyl group are preferred examples. As a carbamate group, -NHCOOR 18 ,-OCONHR 21 (Here, R 18 , R 21 represents an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 or more carbon atoms, an aralkyl group having 7 or more carbon atoms, etc., and -NHCOOR is particularly preferred. 18 ,-OCONHR 21 (Here, R 18 , R 21 represents an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 or more carbon atoms, an aralkyl group having 7 or more carbon atoms. ) and the like.
[0188] The amide group is not particularly limited, and examples thereof include -CONR 16 R 17 、-NR 15 -COR 18 (R 15 ~R 18 As described above. ) and the like, a group containing a carbonyl group and an amino group or an imino group is a preferred example. As an amide group, -NR 15 -COR 18 , more preferably -NHCOR 18 .
[0189] The alkoxysilyl group is not particularly limited, and examples thereof include mono-, di-, or tri-alkoxysilyl groups, preferably an alkoxysilyl group having 1 to 20 carbon atoms, and more preferably an alkoxysilyl group having 1 to 6 carbon atoms. Examples thereof include a methoxysilyl group, an ethoxysilyl group, a tert-butoxysilyl group, a cyclohexylsilyl group, and the groups exemplified in the substituent Z described later.
[0190] Examples of the (meth)acryloyloxy group include an acryloyloxy group and a methacryloyloxy group.
[0191] An acidic group, a group having a basic nitrogen atom, a hydroxyl group, etc. can form a salt.
[0192] The functional group possessed by the polymer forming the polymer binder is preferably an acidic group, an alkoxysilyl group, an amide group, a urea group, a urethane group or an epoxy group, and more preferably an acidic group.
[0193] The polymer forming the polymer binder may have a functional group selected from the functional group group (I) in any of the constituent components forming the polymer, and may have the functional group in either the main chain or the side chain of the polymer.
[0194] There are no particular restrictions on the method of incorporating functional groups into polymer chains, and examples thereof include a method of using as a polymerizable compound copolymerizable with a polymerizable compound having a functional group selected from functional group group (I), a method of using a polymerization initiator or chain transfer agent having (producing) the above-mentioned functional group, a method of utilizing a polymer reaction, etc.
[0195] The content of the functional groups selected from the functional group group (I) in the polymer forming the polymer binder A is not particularly limited. For example, the proportion of the constituents having the functional groups selected from the above-mentioned functional group group (I) in all the constituents constituting the polymer forming the polymer binder is preferably 0.01 to 50 mol%, preferably 0.02 to 49 mol%, more preferably 0.1 to 40 mol%, further preferably 1 to 30 mol%, and particularly preferably 3 to 25 mol%.
[0196] On the other hand, the content of the functional groups selected from the functional group group (I) in the polymer forming the polymer binder B is not particularly limited, and the proportion of the constituent components having the functional groups selected from the above-mentioned functional group group (I) in all the constituent components constituting the polymer forming the polymer binder is preferably 20 mol% or less, preferably 5 mol% or less, more preferably 1 mol% or less, and further preferably 0.7 mol% or less.
[0197] The polymer (each component and raw material compound) forming the polymer binder may have a substituent. The substituent is not particularly limited, but preferably, a group selected from the following substituent Z is mentioned.
[0198] -Substituent Z-
[0199] Alkyl (preferably an alkyl group having 1 to 20 carbon atoms, for example, methyl, ethyl, isopropyl, tert-butyl, pentyl, heptyl, 1-ethylpentyl, benzyl, 2-ethoxyethyl, 1-carboxymethyl, etc.), alkenyl (preferably an alkenyl group having 2 to 20 carbon atoms, for example, vinyl, allyl, oleyl, etc.), alkynyl (preferably an alkynyl group having 2 to 20 carbon atoms, for example, ethynyl, butadiynyl, phenylethynyl, etc.), cycloalkyl (preferably a cycloalkyl group having 3 to 20 carbon atoms, for example, cyclopropyl, cyclopentyl, cyclohexyl, 4-methylcyclohexyl, etc. In the present specification, when it is an alkyl group, it is generally represented by The cycloalkyl group is shown to be included, but is described separately here. ), aryl (preferably an aryl group having 6 to 26 carbon atoms, for example, phenyl, 1-naphthyl, 4-methoxyphenyl, 2-chlorophenyl, 3-methylphenyl, etc.), aralkyl (preferably an aralkyl group having 7 to 23 carbon atoms, for example, benzyl, phenethyl, etc.), heterocyclic group (preferably a heterocyclic group having 2 to 20 carbon atoms, more preferably a 5- or 6-membered heterocyclic group having at least one oxygen atom, sulfur atom, or nitrogen atom. The heterocyclic group includes an aromatic heterocyclic group and an aliphatic heterocyclic group. For example, tetrahydropyranyl, tetrahydrofuranyl, 2-pyridinyl 4-pyridyl, 2-imidazolyl, 2-benzimidazolyl, 2-thiazolyl, 2-oxazolyl, pyrrolidonyl, etc.), alkoxy (preferably an alkoxy group having 1 to 20 carbon atoms, for example, methoxy, ethoxy, isopropoxy, benzyloxy, etc.), aryloxy (preferably an aryloxy group having 6 to 26 carbon atoms, for example, phenoxy, 1-naphthyloxy, 3-methylphenoxy, 4-methoxyphenoxy, etc., and the term "aryloxy" in this specification includes aroyloxy), heterocyclic oxy (a group in which an -O- group is bonded to the above heterocyclic group), alkoxycarbonyl (preferably an alkoxy group having 2 to 20 carbon atoms), oxycarbonyl, for example, ethoxycarbonyl, 2-ethylhexyloxycarbonyl, dodecyloxycarbonyl, etc.), aryloxycarbonyl (preferably aryloxycarbonyl having 6 to 26 carbon atoms, for example, phenoxycarbonyl, 1-naphthyloxycarbonyl, 3-methylphenoxycarbonyl, 4-methoxyphenoxycarbonyl, etc.), amino (preferably amino, alkylamino, arylamino having 0 to 20 carbon atoms, for example, amino (-NH2), N,N-dimethylamino, N,N-diethylamino, N-ethylamino, anilino, etc.), sulfamoyl (preferably sulfamoyl having 0 to 20 carbon atoms, for example, N,N-dimethylsulfamoyl, N-phenylsulfamoyl, etc.), acyl (including alkylcarbonyl, alkenylcarbonyl, alkynylcarbonyl, arylcarbonyl, heterocyclic carbonyl, preferably acyl having 1 to 20 carbon atoms, for example, acetyl, propionyl, butyryl, octanoyl, hexadecanoyl, acryloyl, methacryloyl, crotonyl, benzoyl, naphthoyl, nicotinoyl, etc.), acyloxy (including alkylcarbonyloxy, alkenylcarbonyloxy, alkynylcarbonyloxy, arylcarbonyloxy, heterocyclic carbonyloxy, preferably acyloxy having 1 to 20 carbon atoms, for example, acetyloxy, propionyloxy, butyryloxy, octanoyloxy , hexadecanoyloxy, acryloyloxy, methacryloyloxy, crotonyloxy, benzoyloxy, naphthoyloxy, nicotinyloxy, etc.), aryloxy (preferably aryloxy having 7 to 23 carbon atoms, for example, benzoyloxy, etc.), carbamoyl (preferably carbamoyl having 1 to 20 carbon atoms, for example, N,N-dimethylcarbamoyl, N-phenylcarbamoyl, etc.), acylamino (preferably acylamino having 1 to 20 carbon atoms, for example, acetylamino, benzylamino, etc.), alkylthio (preferably alkylthio having 1 to 20 carbon atoms, for example, methylthio, ethylthio, isopropylthio , benzylthio, etc.), arylthio (preferably arylthio having 6 to 26 carbon atoms, for example, phenylthio, 1-naphthylthio, 3-methylphenylthio, 4-methoxyphenylthio, etc.), heterocyclic thio (a group in which -S- is bonded to the above heterocyclic group), alkylsulfonyl (preferably alkylsulfonyl having 1 to 20 carbon atoms, for example, methylsulfonyl, ethylsulfonyl, etc.), arylsulfonyl (preferably arylsulfonyl having 6 to 22 carbon atoms, for example, benzylsulfonyl, etc.), alkylsilyl (preferably alkylsilyl having 1 to 20 carbon atoms, for example, monomethylsilyl, dimethylsilyl , trimethylsilyl, triethylsilyl, etc.), arylsilyl (preferably arylsilyl having 6 to 42 carbon atoms, for example, triphenylsilyl, etc.), alkoxysilyl (preferably alkoxysilyl having 1 to 20 carbon atoms, for example, monomethoxysilyl, dimethoxysilyl, trimethoxysilyl, triethoxysilyl, etc.), aryloxysilyl (preferably aryloxysilyl having 6 to 42 carbon atoms, for example, triphenoxysilyl, etc.), phosphoryl (preferably phosphate having 0 to 20 carbon atoms, for example, -OP(=O)(R, P ) 2), phosphono group (preferably a phosphono group having 0 to 20 carbon atoms, for example, -P(=O)(R P ) 2), phosphinyl group (preferably a phosphinyl group having 0 to 20 carbon atoms, for example, -P(R P ) 2), sulfo group (sulfonic acid group), carboxyl group, hydroxyl group, sulfanyl group, cyano group, halogen atom (such as fluorine atom, chlorine atom, bromine atom, iodine atom, etc.). P is a hydrogen atom or a substituent (preferably a group selected from the substituent Z).
[0200] Furthermore, each group listed in these substituents Z may be further substituted by the substituents Z described above.
[0201] The above-mentioned alkyl group, alkylene group, alkenyl group, alkenylene group, alkynyl group and / or alkynylene group etc. may be cyclic or chain-shaped, and may be straight-chain or branched.
[0202] (Physical properties or characteristics of polymer binder or polymer forming polymer binder, etc.)
[0203] The polymer forming the polymer binder may be a non-crosslinked polymer or a crosslinked polymer. Furthermore, when the polymer is crosslinked by heating or applying a voltage, the molecular weight may be greater than the above molecular weight. Preferably, when the all-solid-state secondary battery is first used, the mass average molecular weight of the polymer is within the above range.
[0204] The water concentration of the polymer binder (polymer) is preferably 100 ppm (mass basis) or less. The polymer binder may be crystallized and dried, or a polymer binder dispersion may be used as it is.
[0205] The polymer forming the polymer binder is preferably amorphous. In the present invention, the polymer being "amorphous" typically means that no endothermic peak due to melting of crystals is observed when measured at the glass transition temperature.
[0206] The mass average molecular weight of each polymer forming the polymer binders A and B is not particularly limited and can be appropriately determined.
[0207] The mass average molecular weight of each polymer forming the polymer binder A is, for example, preferably 15,000 or more, more preferably 30,000 or more, and further preferably 50,000 or more. The upper limit is substantially 5,000,000 or less, preferably 4,000,000 or less, and more preferably 3,000,000 or less.
[0208] The mass average molecular weight of the polymer forming the polymer binder B is, for example, preferably 20,000 or more, more preferably 50,000 or more, and further preferably 200,000 or more. The upper limit is substantially 5,000,000 or less, preferably 4,000,000 or less, and more preferably 3,000,000 or less.
[0209] - Determination of Molecular Weight -
[0210] In the present invention, the molecular weight of a polymer, a polymer chain and a macromonomer, unless otherwise specified, refers to the mass average molecular weight and number average molecular weight calculated by standard polystyrene obtained by gel permeation chromatography (GPC). As a determination method thereof, it is basically set to the value measured by the method of the following condition 1 or condition 2 (preferred). Among them, a suitable eluent can be appropriately selected and used according to the type of polymer or macromonomer.
[0211] (Condition 1)
[0212] Column: Two TOSOH TSKgel Super AWM-H (trade name, manufactured by TOSOH CORPORATION) connected
[0213] Carrier: 10mM LiBr / N-methylpyrrolidone
[0214] Measurement temperature: 40℃
[0215] Carrier flow rate: 1.0ml / min
[0216] Sample concentration: 0.1 mass%
[0217] Detector: RI (refractive index) detector
[0218] (Condition 2)
[0219] Column: A column connected with TOSOH TSKgel Super HZM-H, TOSOH TSKgel Super HZ4000, or TOSOH TSKgel Super HZ2000 (all trade names, manufactured by Tosoh Corporation) was used.
[0220] Carrier: Tetrahydrofuran
[0221] Measurement temperature: 40℃
[0222] Carrier flow rate: 1.0ml / min
[0223] Sample concentration: 0.1 mass%
[0224] Detector: RI (refractive index) detector
[0225] Specific examples of the polymer forming the polymer binder include the polymers synthesized in the examples, but the present invention is not limited to these.
[0226] <Dispersion Medium>
[0227] The inorganic solid electrolyte-containing composition of the present invention preferably contains a dispersion medium as a dispersion medium for dispersing or dissolving the above-mentioned components, and is more preferably in the form of a slurry.
[0228] The dispersion medium may be any organic compound that is liquid in the use environment, and examples thereof include various solvents. Specific examples thereof include alcohol compounds, ether compounds, amide compounds, amine compounds, ketone compounds, aromatic compounds, aliphatic compounds, nitrile compounds, and ester compounds.
[0229] The dispersion medium may be a non-polar dispersion medium (hydrophobic dispersion medium) or a polar dispersion medium (hydrophilic dispersion medium), and is preferably a non-polar dispersion medium from the viewpoint of being able to exhibit excellent dispersibility. A non-polar dispersion medium generally refers to a dispersion medium having a low affinity for water, but in the present invention, a dispersion medium having a CLogP value of 1.5 to 6 is preferred, and examples thereof include ester compounds, ketone compounds, ether compounds, aromatic compounds, aliphatic compounds, and the like.
[0230] Examples of the alcohol compound include methanol, ethanol, 1-propanol, 2-propanol, 2-butanol, ethylene glycol, propylene glycol, glycerol, 1,6-hexanediol, cyclohexanediol, sorbitol, xylitol, 2-methyl-2,4-pentanediol, 1,3-butanediol, and 1,4-butanediol.
[0231] Examples of the ether compound include alkylene glycols (diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, etc.), alkylene glycol monoalkyl ethers (ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, diethylene glycol monobutyl ether, diethylene glycol monobutyl ether, etc.), alkylene glycol dialkyl ethers (ethylene glycol dimethyl, etc.), dialkyl ethers (dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, etc.), and cyclic ethers (tetrahydrofuran, dioxane (including 1,2-, 1,3-, and 1,4-isomers), etc.).
[0232] Examples of the amide compound include N,N-dimethylformamide, N-methyl-2-pyrrolidone, 2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, ε-caprolactam, formamide, N-methylformamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpropaneamide, and hexamethylphosphoric triamide.
[0233] Examples of the amine compound include triethylamine, diisopropylethylamine, and tri-n-butylamine.
[0234] Examples of the ketone compound include acetone, methyl ethyl ketone, methyl isobutyl ketone (MIBK), cyclopentanone, cyclohexanone, cycloheptanone, dipropyl ketone, dibutyl ketone, diisopropyl ketone, diisobutyl ketone (DIBK), isobutyl propyl ketone, sec-butyl propyl ketone, amyl propyl ketone, and butyl propyl ketone.
[0235] Examples of the aromatic compound include benzene, toluene, and xylene.
[0236] Examples of the aliphatic compound include hexane, heptane, octane, decane, cyclohexane, methylcyclohexane, ethylcyclohexane, cyclooctane, decalin, paraffin, gasoline, naphtha, kerosene, and light oil.
[0237] Examples of the nitrile compound include acetonitrile, propionitrile, and isobutyronitrile.
[0238] Examples of the ester compound include ethyl acetate, butyl acetate, propyl acetate, propyl butyrate, isopropyl butyrate, butyl butyrate, isobutyl butyrate, butyl valerate, ethyl isobutyrate, propyl isobutyrate, isopropyl isobutyrate, isobutyl isobutyrate, propyl pivalate, isopropyl pivalate, butyl pivalate, and isobutyl pivalate.
[0239] In the present invention, among these, ether compounds, ketone compounds, aromatic compounds, aliphatic compounds, and ester compounds are preferred, and ester compounds, ketone compounds, and ether compounds are more preferred.
[0240] The number of carbon atoms in the compound constituting the dispersion medium is not particularly limited, but is preferably 2 to 30, more preferably 4 to 20, further preferably 6 to 15, and particularly preferably 7 to 12.
[0241] The compound constituting the dispersion medium preferably has a CLogP value of 1 or more, more preferably 1.5 or more, further preferably 2 or more, and particularly preferably 3 or more. The upper limit is not particularly limited, but is practically 10 or less, and preferably 6 or less.
[0242] In the present invention, the CLogP value refers to a value obtained by calculating the common logarithm LogP of the partition coefficient P between 1-octanol and water. A known method or software can be used for calculating the CLogP value, and unless otherwise specified, the structure is drawn using ChemDraw from PerkinElmer and the result is a calculated value.
[0243] When two or more dispersion media are contained, the ClogP value of the dispersion medium is defined as the sum of the products of the ClogP values and the mass fractions of the respective dispersion media.
[0244] If such dispersion media are listed from the above, there are toluene (CLogP=2.5), xylene (ClogP=3.12), hexane (CLogP=3.9), heptane (Hep, CLogP=4.4), octane (CLogP=4.9), cyclohexane (CLogP=3.4), cyclooctane (CLogP=4.5), decalin (CLogP=4.8), diisobutyl ketone (DIBK, CLogP=3.0), dibutyl ether (DBE, CLogP=2.57), butyl butyrate (CLogP=2.8), tributylamine (CLogP=4.8), methyl isobutyl ketone (MIBK, ClogP=1.31), ethylcyclohexane (ECH, ClogP=3.4), etc.
[0245] The compound constituting the dispersion medium may have an SP value (MPa) from the viewpoint of the dispersibility of the solid particles. 1 / 2 ) is preferably 9-21, more preferably 10-20, and further preferably 11-19.
[0246] The SP value of the dispersion medium is the SP value calculated by the above-mentioned Hoy method converted into a unit of MPa. 1 / 2 When the inorganic solid electrolyte composition contains two or more dispersion media, the SP value of the dispersion medium refers to the SP value of the entire dispersion medium, and is set to the sum of the products of the SP value of each dispersion medium and the mass fraction. Specifically, it is calculated in the same manner as the calculation method of the SP value of the above-mentioned polymer, except that the SP value of each dispersion medium is used instead of the SP value of the constituent component.
[0247] The boiling point of the dispersion medium at normal pressure (1 atmosphere) is preferably 50° C. or higher, more preferably 70° C. or higher. The upper limit is preferably 250° C. or lower, more preferably 220° C. or lower.
[0248] The inorganic solid electrolyte-containing composition may contain the above-mentioned dispersion medium alone or in combination of two or more.
[0249] In the present invention, the content of the dispersion medium in the inorganic solid electrolyte composition is not particularly limited and can be appropriately set. For example, in the inorganic solid electrolyte composition, it is preferably 20 to 80% by mass, more preferably 30 to 70% by mass, and particularly preferably 40 to 60% by mass.
[0250] <Active substances>
[0251] The inorganic solid electrolyte composition of the present invention may further contain an active material capable of inserting and extracting ions of metals belonging to Group 1 or Group 2 of the periodic table. The active material is described below, and examples thereof include positive electrode active materials and negative electrode active materials.
[0252] In the present invention, an inorganic solid electrolyte composition containing an active material (positive electrode active material or negative electrode active material) may be referred to as an electrode composition (positive electrode composition or negative electrode composition).
[0253] (Positive electrode active material)
[0254] The positive electrode active material is preferably a positive electrode active material that can reversibly insert and remove lithium ions. As long as the material has the above-mentioned properties, there is no particular limitation, and it may be a transition metal oxide or an element that can form a complex with Li, such as sulfur.
[0255] Among them, as the positive electrode active material, it is preferred to use a transition metal oxide, and more preferably a transition metal element M a (one or more elements selected from Co, Ni, Fe, Mn, Cu and V) transition metal oxide. In addition, the element M may be mixed in the transition metal oxide. b (Metals other than lithium, elements of Group 1 (Ia) of the periodic table, elements of Group 2 (IIa), Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, B, etc.) As a mixed amount, it is preferred to have an amount of 1:1 relative to the transition metal element M a The amount of Li / M is preferably 0 to 30 mol%. a The components are mixed and synthesized so that the molar ratio of them becomes 0.3 to 2.2.
[0256] Specific examples of transition metal oxides include (MA) transition metal oxides having a layered rock salt structure, (MB) transition metal oxides having a spinel structure, (MC) lithium-containing transition metal phosphate compounds, (MD) lithium-containing transition metal halophosphate compounds, and (ME) lithium-containing transition metal silicate compounds.
[0257] Specific examples of transition metal oxides having a layered rock salt structure (MA) include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).
[0258] Specific examples of the transition metal oxide (MB) having a spinel structure include LiMn2O4 (LMO), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8 and Li2NiMn3O8.
[0259] As (MC) lithium-containing transition metal phosphate compounds, for example, olivine-type iron phosphates such as LiFePO4 and Li3Fe2(PO4)3, pyrophosphates such as LiFeP2O7, cobalt phosphates such as LiCoPO4, and monoclinic NASICON-type vanadium phosphates such as Li3V2(PO4)3 (lithium vanadium phosphate) can be listed.
[0260] Examples of the (MD) lithium-containing transition metal halophosphate compound include iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.
[0261] Examples of the (ME) lithium-containing transition metal silicate compound include Li2FeSiO4, Li2MnSiO4, and Li2CoSiO4.
[0262] In the present invention, (MA) is preferably a transition metal oxide having a layered rock salt structure, and more preferably LCO or NMC.
[0263] The shape of the positive electrode active material is not particularly limited, and is preferably in the form of particles. The particle size (volume average particle size) of the positive electrode active material is not particularly limited. For example, it can be set to 0.1 to 50 μm. The particle size of the positive electrode active material particles can be measured in the same manner as the particle size of the above-mentioned inorganic solid electrolyte. In order to make the positive electrode active material a specified particle size, a conventional pulverizer or classifier is used. For example, a mortar, a ball mill, a sand mill, a vibrating ball mill, a satellite ball mill, a planetary ball mill, and a rotary airflow type jet mill or a sieve can be appropriately used. During pulverization, wet pulverization in which a dispersion medium such as water or methanol coexists can also be appropriately performed. In order to set the desired particle size, it is preferably classified. The classification is not particularly limited, and can be performed using a sieve, a wind classifier, etc. Both dry and wet classification can be used.
[0264] The positive electrode active material obtained by the calcination method may be used after being washed with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.
[0265] The positive electrode active material may be used alone or in combination of two or more.
[0266] When a positive electrode active material layer is formed, the positive electrode active material layer has a unit area (cm 2The mass (mg) (weight per unit area) of the positive electrode active material is not particularly limited. It can be appropriately determined according to the designed battery capacity, for example, it can be set to 1 to 100 mg / cm 2 .
[0267] The content of the positive electrode active material in the inorganic solid electrolyte composition is not particularly limited, but is preferably 10 to 97% by mass, more preferably 30 to 95% by mass, further preferably 40 to 93% by mass, and particularly preferably 50 to 90% by mass, based on 100% by mass of the solid content.
[0268] (Negative electrode active material)
[0269] The negative electrode active material is preferably a negative electrode active material that can reversibly embed and deintercalate lithium ions. The material is not particularly limited as long as it has the above-mentioned characteristics, and carbonaceous materials, metal oxides, metal composite oxides, lithium monomers, lithium alloys, negative electrode active materials that can form alloys with lithium, etc. can be listed. Among them, from the perspective of reliability, carbonaceous materials, metal composite oxides or lithium monomers are preferably used.
[0270] The carbonaceous material used as the negative electrode active material refers to a material substantially composed of carbon. For example, carbon black such as petroleum pitch, acetylene black (AB), graphite (natural graphite, artificial graphite such as vapor-grown graphite, etc.), and various synthetic resins such as PAN (polyacrylonitrile) resin or furfuryl alcohol resin can be calcined to form the carbonaceous material. In addition, various carbon fiber types such as PAN-based carbon fiber, cellulose-based carbon fiber, asphalt-based carbon fiber, vapor-grown carbon fiber, dehydrated PVA (polyvinyl alcohol)-based carbon fiber, lignin carbon fiber, glassy carbon fiber and activated carbon fiber, mesophase microspheres, graphite whiskers and flat graphite can also be listed.
[0271] These carbonaceous materials are divided into difficult graphitization carbonaceous materials (also referred to as hard carbon) and graphite-based carbonaceous materials by the degree of graphitization. In addition, the carbonaceous material preferably has the surface spacing or density and crystallite size recorded in Japanese Patent Publication No. 62-22066, Japanese Patent Publication No. 2-6856, and Japanese Patent Publication No. 3-45473. Carbonaceous materials do not need to be a single material, and a mixture of natural graphite and artificial graphite recorded in Japanese Patent Publication No. 5-90844, and graphite with a coating layer recorded in Japanese Patent Publication No. 6-4516 can also be used.
[0272] As the carbonaceous material, hard carbon or graphite is preferably used, and graphite is more preferably used.
[0273] As oxides of metal or semi-metal elements suitable as negative electrode active materials, there are no particular restrictions as long as they are oxides that can absorb and release lithium, and examples include oxides of metal elements (metal oxides), composite oxides of metal elements or composite oxides of metal elements and semi-metal elements (collectively referred to as metal composite oxides), and oxides of semi-metal elements (semi-metal oxides). As these oxides, amorphous oxides are preferred, and further preferred examples are chalcogenides, which are reaction products of metal elements and elements of Group 16 of the periodic table. In the present invention, semi-metal elements refer to elements that show properties intermediate between metal elements and non-semi-metal elements, and generally include six elements of boron, silicon, germanium, arsenic, antimony and tellurium, and further include three elements of selenium, polonium and astatine. In addition, amorphous refers to a material having a broad scattering band with a vertex in the region of 20° to 40° at a 2θ value by an X-ray diffraction method using CuKα rays, and may also have crystalline diffraction lines. The strongest intensity among the crystalline diffraction lines appearing in the region of 40° to 70° at 2θ values is preferably 100 times or less, more preferably 5 times or less, the intensity of the diffraction line at the top of the broad scattering band appearing in the region of 20° to 40° at 2θ values, and particularly preferably a diffraction line without crystallinity.
[0274] Among the compound groups including the above-mentioned amorphous oxides and chalcogenides, amorphous oxides of semimetallic elements or the above-mentioned chalcogenides are more preferred, and (complex) oxides or chalcogenides containing one or a combination of two or more elements selected from Groups 13 (IIIB) to 15 (VB) of the periodic table (e.g., Al, Ga, Si, Sn, Ge, Pb, Sb, and Bi) are particularly preferred. Specific examples of preferred amorphous oxides and chalcogenides include, for example, Ga2O3, GeO, PbO, PbO2, Pb2O3, Pb2O4, Pb3O4, Sb2O3, Sb2O4, Sb2O8Bi2O3, Sb2O8Si2O3, Sb2O5, Bi2O3, Bi2O4, GeS, PbS, PbS2, Sb2S3, or Sb2S5.
[0275] Preferred negative electrode active materials that can be used together with the amorphous oxide negative electrode active material based on Sn, Si, or Ge include carbonaceous materials that can absorb and / or release lithium ions or lithium metal, lithium monomers, lithium alloys, and negative electrode active materials that can alloy with lithium.
[0276] From the viewpoint of high current density charge and discharge characteristics, the oxide of metal or semimetal element, especially metal (composite) oxide and the above-mentioned chalcogenide preferably contains at least one of titanium and lithium as a constituent component. As the metal composite oxide containing lithium (lithium composite metal oxide), for example, composite oxides of lithium oxide and the above-mentioned metal (composite) oxide or the above-mentioned chalcogenide can be listed, and more specifically, Li2SnO2 can be listed.
[0277] The negative electrode active material, such as a metal oxide, preferably contains titanium (titanium oxide). Specifically, due to Li4Ti5O 12 (Lithium titanate [LTO]) has a small volume change when absorbing and releasing lithium ions, and therefore has excellent rapid charge and discharge characteristics, and is preferred in terms of suppressing electrode degradation and being able to extend the life of lithium ion secondary batteries.
[0278] The lithium alloy as the negative electrode active material is not particularly limited as long as it is an alloy generally used as a negative electrode active material for secondary batteries, and examples thereof include lithium aluminum alloys.
[0279] The negative electrode active material that can form an alloy with lithium is not particularly limited as long as it is a negative electrode active material commonly used as a secondary battery. Since this active material expands and contracts due to charging and discharging, the cohesiveness of the solid particles is reduced, but in the present invention, high cohesiveness can be achieved by using the above-mentioned polymer binder A and binder B. As such an active material, (negative electrode) active materials (alloys) with silicon or tin elements, metals such as Al and In can be cited, preferably negative electrode active materials (active materials containing silicon elements) with silicon elements that can achieve higher battery capacity, more preferably active materials containing silicon elements with a silicon content of more than 50 mol% of all constituent elements.
[0280] Generally, the negative electrode containing these negative electrode active materials (Si negative electrode containing active materials containing silicon elements, Sn negative electrode containing active materials having tin elements, etc.) can absorb more Li ions compared with carbon negative electrodes (graphite and acetylene black, etc.). That is, the amount of Li ions absorbed per unit mass increases. Therefore, the battery capacity can be increased. As a result, it has the advantage of being able to extend the battery driving time.
[0281] As active materials containing silicon elements, for example, silicon materials such as Si and SiOx (0<x≤1), and silicon-containing alloys (for example, LaSi2, VSi2, La-Si, Gd-Si, Ni-Si) or organized active materials (for example, LaSi2 / Si) containing titanium, vanadium, chromium, manganese, nickel, copper, lanthanum, etc., and active materials containing silicon elements such as SnSiO3 and SnSiS3 and tin elements, etc. can be listed. In addition, SiOx itself can be used as a negative electrode active material (semi-metallic oxide), and Si is generated by the operation of an all-solid-state secondary battery, so it can be used as a negative electrode active material (its precursor material) that can be alloyed with lithium.
[0282] Examples of negative electrode active materials containing tin include Sn, SnO, SnO2, SnS, SnS2, and active materials containing the above silicon and tin elements, etc. Also, composite oxides with lithium oxide, such as Li2SnO2, can be cited.
[0283] In the present invention, the above-mentioned negative electrode active material can be used without particular restrictions, but from the viewpoint of battery capacity, as the negative electrode active material, it is preferably a negative electrode active material that can alloy with lithium, among which the above-mentioned silicon material or silicon-containing alloy (alloy containing silicon element) is more preferred, and it is further preferred to contain silicon (Si) or a silicon-containing alloy.
[0284] As a measurement method, inductively coupled plasma (ICP) emission spectrometry can be used. As a simple method, the chemical formula of the compound obtained by the above-mentioned calcination method can be calculated from the mass difference of the powder before and after calcination.
[0285] The shape of the negative electrode active material is not particularly limited, and is preferably in the form of particles. The volume average particle size of the negative electrode active material is not particularly limited, and is preferably 0.1 to 60 μm. The volume average particle size of the negative electrode active material particles can be measured in the same manner as the average particle size of the inorganic solid electrolyte. In order to set the particle size to a predetermined size, a conventional pulverizer or classifier is used in the same manner as the positive electrode active material.
[0286] The above-mentioned negative electrode active materials may be used alone or in combination of two or more.
[0287] When forming a negative electrode active material layer, the negative electrode active material layer has a unit area (cm 2 The mass (mg) (weight per unit area) of the negative electrode active material is not particularly limited. It can be appropriately determined according to the designed battery capacity, for example, it can be set to 1 to 100 mg / cm 2 .
[0288] The content of the negative electrode active material in the inorganic solid electrolyte composition is not particularly limited, but is preferably 10 to 90% by mass, more preferably 20 to 85% by mass, more preferably 30 to 80% by mass, and even more preferably 40 to 75% by mass based on 100% by mass of the solid content.
[0289] In the present invention, when the negative electrode active material layer is formed by charging the secondary battery, ions of metals belonging to the first or second group of the periodic table generated in the all-solid-state secondary battery can be used instead of the above-mentioned negative electrode active material. The negative electrode active material layer can be formed by bonding the ions with electrons to precipitate as metal.
[0290] (Encapsulation of active substances)
[0291] The surfaces of the positive electrode active material and the negative electrode active material can also be coated with different metal oxides. As the surface coating agent, metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si or Li can be listed. Specifically, titanate spinel, tantalum oxide, niobium oxide, lithium niobate compounds, etc. can be listed. Specifically, Li4Ti5O 12 , Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3, B2O3, etc.
[0292] Furthermore, the surface of the electrode including the positive electrode active material or the negative electrode active material may be surface-treated with sulfur or phosphorus.
[0293] Furthermore, the surface of the particles of the positive electrode active material or the negative electrode active material may be subjected to a surface treatment using actinic rays or an active gas (plasma, etc.) before and after the above-mentioned surface coating.
[0294] <Conductive additive>
[0295] The inorganic solid electrolyte-containing composition of the present invention may appropriately contain a conductive auxiliary agent, and in particular, a silicon atom-containing active material as a negative electrode active material is preferably used together with a conductive auxiliary agent.
[0296] There are no particular restrictions on the conductive aid, and generally known conductive aids can be used. For example, graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjenblack, and furnace black, amorphous carbon such as needle coke, carbon fibers such as vapor-grown carbon fibers or carbon nanotubes, carbonaceous materials such as graphene or fullerene, and metal powders and metal fibers such as copper and nickel can be used. Conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, and polyphenylene derivatives can also be used.
[0297] In the present invention, when an active material and a conductive aid are used in combination, among the conductive aids, when the battery is charged and discharged, the ions (preferably Li ions) of metals belonging to the first or second group of the periodic table are not embedded and deintercalated, and those that do not function as active materials are used as conductive aids. Therefore, among the conductive aids, those that can function as active materials in the active material layer when the battery is charged and discharged are classified as active materials rather than conductive aids. Whether or not to function as an active material when the battery is charged and discharged is determined by the combination with the active material, rather than being determined in general.
[0298] The conductive auxiliary agent may be contained alone or in combination of two or more.
[0299] The shape of the conductive auxiliary agent is not particularly limited, but is preferably in the form of particles.
[0300] When the inorganic solid electrolyte-containing composition of the present invention contains a conductive auxiliary agent, the content of the conductive auxiliary agent in the inorganic solid electrolyte-containing composition is preferably 0 to 10% by mass in 100% by mass of the solid content.
[0301] <Lithium Salt>
[0302] The inorganic solid electrolyte-containing composition of the present invention preferably further contains a lithium salt (supporting electrolyte).
[0303] The lithium salt is preferably a lithium salt commonly used for such products, without particular limitation. For example, the lithium salts described in paragraphs 0082 to 0085 of JP-A-2015-088486 are preferred.
[0304] When the inorganic solid electrolyte composition of the present invention contains a lithium salt, the content of the lithium salt is preferably 0.1 parts by mass or more, more preferably 5 parts by mass or more, relative to 100 parts by mass of the solid electrolyte, and the upper limit is preferably 50 parts by mass or less, more preferably 20 parts by mass or less.
[0305] <Dispersant>
[0306] In the inorganic solid electrolyte composition of the present invention, the above-mentioned polymer binder also acts as a dispersant, so it may not contain a dispersant other than the polymer binder, or it may contain a dispersant. As a dispersant, a dispersant commonly used in all-solid-state secondary batteries can be appropriately selected for use. Usually, the desired compound in particle adsorption, spatial repulsion and / or electrostatic repulsion is appropriately used.
[0307] <Other additives>
[0308] The inorganic solid electrolyte composition of the present invention can appropriately contain ionic liquids, thickeners, crosslinking agents (substances that undergo crosslinking reactions by free radical polymerization, polycondensation or ring-opening polymerization, etc.), polymerization initiators (substances that generate acids or free radicals by heat or light, etc.), defoamers, leveling agents, dehydrating agents, antioxidants, etc. as other ingredients other than the above-mentioned components. Ionic liquids are liquids contained in order to further improve ionic conductivity, and known liquids can be used without particular restrictions. In addition, polymers other than the above-mentioned polymers, commonly used binders, etc. may be contained.
[0309] (Preparation of Inorganic Solid Electrolyte Composition)
[0310] The inorganic solid electrolyte-containing composition of the present invention can be prepared as a mixture, preferably as a slurry, by mixing the inorganic solid electrolyte, the above-mentioned polymer binder, the dispersion medium, an appropriate lithium salt, and any other components in various commonly used mixers.
[0311] The mixing method is not particularly limited, and the mixture may be mixed all at once or sequentially. The mixing environment is not particularly limited, and examples thereof include dry air or inert gas.
[0312] The active material layer-forming composition of the present invention suppresses (re)aggregation of solid particles, and can be a dispersion containing solid particles highly dispersed for a long period of time.
[0313] [Sheet for all-solid-state secondary batteries]
[0314] The sheet material for all-solid-state secondary batteries of the present invention is a sheet-like molded body capable of forming a constituent layer of an all-solid-state secondary battery, and includes various modes according to its use. For example, a sheet material preferably used for a solid electrolyte layer (also referred to as a solid electrolyte sheet for an all-solid-state secondary battery), a sheet material preferably used for a laminate of an electrode or an electrode and a solid electrolyte layer (electrode sheet for an all-solid-state secondary battery), etc. can be cited. In the present invention, these various sheets are sometimes collectively referred to as sheets for all-solid-state secondary batteries.
[0315] The solid electrolyte sheet for all-solid-state secondary batteries of the present invention can be a sheet having a solid electrolyte layer, and can be a sheet having a solid electrolyte layer formed on a substrate, or can be a sheet having no substrate and formed by a solid electrolyte layer. The solid electrolyte sheet for all-solid-state secondary batteries can also have other layers in addition to the solid electrolyte layer. As other layers, for example, a protective layer (peel-off sheet), a current collector, a coating, etc. can be cited.
[0316] As a solid electrolyte sheet for an all-solid-state secondary battery of the present invention, for example, a sheet having a layer composed of the inorganic solid electrolyte composition of the present invention, a common solid electrolyte layer and a protective layer in sequence on a substrate can be cited. The solid electrolyte layer possessed by the solid electrolyte sheet for an all-solid-state secondary battery is preferably formed by the inorganic solid electrolyte composition of the present invention. The content of each component in the solid electrolyte layer is not particularly limited, and the preferred meaning is the same as the content of each component in the solid component of the inorganic solid electrolyte composition of the present invention. The thickness of each layer constituting the solid electrolyte sheet for an all-solid-state secondary battery is the same as the thickness of each layer described in the all-solid-state secondary battery described later.
[0317] As a substrate, as long as it is a substrate that can support a solid electrolyte layer, there is no particular limitation, and the sheet body (plate body) etc. such as the material described in the collector described later, an organic material, an inorganic material etc. can be cited. As an organic material, various polymers etc. can be cited, specifically, polyethylene terephthalate, polypropylene, polyethylene and cellulose etc. can be cited. As an inorganic material, for example, glass and ceramics etc. can be cited.
[0318] The electrode sheet for all-solid-state secondary batteries of the present invention (also referred to as "electrode sheet" for short) can be an electrode sheet with an active material layer, and can be a sheet in which the active material layer is formed on a substrate (collector), or can be a sheet formed by an active material layer without a substrate. The electrode sheet is usually a sheet having a collector and an active material layer, but also includes a form having a collector, an active material layer and a solid electrolyte layer in sequence, and a form having a collector, an active material layer, a solid electrolyte layer and an active material layer in sequence. The solid electrolyte layer and active material layer possessed by the electrode sheet are preferably formed by the inorganic solid electrolyte composition of the present invention. The content of each component in the solid electrolyte layer or the active material layer is not particularly limited, and the preferred meaning is the same as the content of each component in the solid component of the inorganic solid electrolyte composition (electrode composition) of the present invention. The thickness of each layer constituting the electrode sheet of the present invention is the same as the thickness of each layer described in the all-solid-state secondary battery described later. The electrode sheet of the present invention may have the above-mentioned other layers.
[0319] In the sheet material for all-solid-state secondary batteries of the present invention, at least one layer in the solid electrolyte layer and the active material layer is formed by the inorganic solid electrolyte composition of the present invention, and the solid particles in the layer are firmly bonded while fully ensuring the interface contact with each other. In addition, the active material layer formed by the inorganic solid electrolyte composition of the present invention in the electrode sheet for all-solid-state secondary batteries is also firmly bonded to the collector. Therefore, the sheet material for all-solid-state secondary batteries of the present invention is suitable for use as a sheet material capable of forming a constituent layer of an all-solid-state secondary battery.
[0320] In the sheet material for all-solid-state secondary batteries of the present invention, from the viewpoint of being able to achieve enhanced adhesion and reduced battery resistance at a higher level, the layer composed of the inorganic solid electrolyte composition of the present invention is preferably a layer of a heated and dried product containing an inorganic solid electrolyte composition at a temperature above the crystallization temperature of the polymer binder B in the inorganic solid electrolyte composition. The heated and dried product is formed by a polymer binder B composed of a crystalline polymer that is temporarily melted and recrystallized during the formation process of the constituent layer (film formation process containing an inorganic solid electrolyte composition), and solid particles bonded by a particulate polymer binder A. As a result, the solid particles are firmly bonded to each other without showing an increase in interface resistance, thereby being able to take into account both the suppression of the increase in interface resistance and the firm bonding between the solid particles at a higher level.
[0321] The layer composed of the inorganic solid electrolyte composition of the present invention is preferably 10 μm thick in any cross section. 2 The cross-sectional area includes more than 30 particulate regions derived from the polymer binder. The particulate region is a planar area divided by the polymer binder contained in the layer and refers to a granular (blocky) region appearing in the cross-sectional area, which is distinguished from the membrane-like region on the surface of the coating solid particles. As long as the particulate region is a region derived from the polymer binder, the type of polymer binder is not particularly limited, and for example, a particulate region derived from polymer binder A and a particulate region derived from polymer binder B can be cited.
[0322] In the present invention, if the cross-sectional area contains 30 or more particle-shaped regions, the adhesion enhancement and interface resistance reduction caused by the polymer binder B can be effectively enhanced. From the viewpoint of being able to achieve a higher level of suppression of the increase in interface resistance and strong adhesion between solid particles, it is more preferable to have a cross-sectional area of 10 μm or more. 2 The cross-sectional area of the embodiment of the present invention contains 40 or more particle-shaped regions, and more preferably contains 50 or more particle-shaped regions. The upper limit of the number of particle-shaped regions is not particularly limited, but from the viewpoint of interface resistance, the particle-shaped regions of 10 μm are preferably 0.1 μm. 2The number of cross-sectional regions is preferably 300 or less, more preferably 200 or less, and further preferably 150 or less. In the present invention, the number of particulate regions can be appropriately adjusted in the polymer binder, particularly by adjusting the content or average particle size of the polymer binder A and the above-mentioned functional groups.
[0323] After the constituent layers are cut at an arbitrary cross section, the cross section is cut out by ion milling and the number of granular regions is observed at a magnification of 10,000 times. This observation is performed at 10 cross-sectional regions and the average is taken as the number of granular regions.
[0324] (Conditions for cutting out the cross section by ion milling)
[0325] The constituent layer cross section was cut out using an ion milling device (trade name: IM4000PLUS, manufactured by Hitachi, Ltd.) under the conditions of an acceleration voltage of 3 kV, a discharge voltage of 1.5 V, a treatment time of 4 hours, and an argon gas flow rate of 0.1 mL / min. The constituent layer cross section was observed using a scanning electron microscope (SEM, trade name: JSM-7401F, manufactured by JEOL Ltd.) at a magnification of 10,000 times.
[0326] (Observation conditions and method for identifying particle-shaped areas)
[0327] In this cross-sectional observation, a mapping cross-sectional image is obtained by gray-converting an image obtained using ImageJ (trade name, manufactured by National Institutes of Health (NIH)) and converting it into 4-values. In the obtained image, the contrast is highest in the void portion, followed by the region derived from the binder, followed by the region derived from the conductive aid, and the region derived from the active material and the solid electrolyte layer. From the mapping cross-sectional image, a block region (region with a high contrast after the void) containing the position of the carbon atoms derived from the polymer forming the polymer binder is extracted, and the number of the block regions is calculated as the number of particle-like regions.
[0328] When an all-solid-state secondary battery is produced using the all-solid-state secondary battery sheet of the present invention having the above-mentioned structure, excellent battery performance (battery resistance and cycle characteristics) is exhibited.
[0329] [Method for producing a sheet for an all-solid-state secondary battery]
[0330] The manufacturing method of the sheet material for all-solid-state secondary batteries of the present invention is not particularly limited, and the above-mentioned layers can be formed using the inorganic solid electrolyte composition of the present invention. For example, it is preferred to cite a method of forming a layer (coating and drying layer) composed of an inorganic solid electrolyte composition on a substrate or a collector (may be via another layer.). Thus, it is possible to prepare a sheet material for all-solid-state secondary batteries having a substrate or a collector and a coating and drying layer, preferably a coating and drying layer composed of a heated and dried product containing an inorganic solid electrolyte composition. Here, the coating and drying layer refers to a layer formed by coating the inorganic solid electrolyte composition of the present invention and drying the dispersion medium (that is, a layer formed using the inorganic solid electrolyte composition of the present invention and removing the dispersion medium from the inorganic solid electrolyte composition of the present invention). As long as the active material layer and the coating and drying layer are within the range that does not damage the effect of the present invention, the dispersion medium can remain, and as a residual amount, for example, in each layer, it can be set to 3% by mass or less.
[0331] In the method for producing the sheet for an all-solid-state secondary battery of the present invention, each step such as coating and drying will be described below in the method for producing an all-solid-state secondary battery.
[0332] In the method for producing the all-solid-state secondary battery sheet of the present invention, the applied dried layer obtained in the above manner may be pressurized. The pressurization conditions and the like will be described in the method for producing the all-solid-state secondary battery described later.
[0333] Furthermore, in the method for producing the sheet for an all-solid-state secondary battery of the present invention, the substrate, the protective layer (particularly the release sheet), and the like can also be peeled off.
[0334] [All-solid-state secondary battery]
[0335] The all-solid-state secondary battery of the present invention comprises a positive electrode active material layer, a negative electrode active material layer opposite to the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. The positive electrode active material layer is preferably formed on the positive electrode collector and constitutes the positive electrode. The negative electrode active material layer is preferably formed on the negative electrode collector and constitutes the negative electrode.
[0336] At least one of the negative electrode active material layer, the positive electrode active material layer and the solid electrolyte layer is preferably formed by the inorganic solid electrolyte composition of the present invention, and it is also preferred that all layers are formed by the inorganic solid electrolyte composition of the present invention. For the types of components contained and their content ratios, the active material layer or solid electrolyte layer formed by the inorganic solid electrolyte composition of the present invention is preferably the same as the solid component of the inorganic solid electrolyte composition of the present invention. In addition, when the active material layer or the solid electrolyte layer is not formed by the inorganic solid electrolyte composition of the present invention, known materials can be used.
[0337] The thickness of each of the negative electrode active material layer, the solid electrolyte layer and the positive electrode active material layer is not particularly limited. Considering the size of a general all-solid-state secondary battery, the thickness of each layer is preferably 10 to 1,000 μm, more preferably 20 μm or more and less than 500 μm. In the all-solid-state secondary battery of the present invention, the thickness of at least one of the positive electrode active material layer and the negative electrode active material layer is further preferably 50 μm or more and less than 500 μm.
[0338] Each of the positive electrode active material layer and the negative electrode active material layer may include a current collector on the side opposite to the solid electrolyte layer.
[0339] <Frame>
[0340] The all-solid-state secondary battery of the present invention can be used as an all-solid-state secondary battery in the state of the above structure according to the purpose, but in order to make it in the form of a dry cell, it is preferably further enclosed in an appropriate shell for use. The shell can be a metallic shell or a resin (plastic) shell. In the case of using a metallic shell, for example, a shell made of aluminum alloy or stainless steel can be cited. Preferably, the metallic shell is divided into a positive electrode side shell and a negative electrode side shell and is electrically connected to the positive electrode collector and the negative electrode collector, respectively. Preferably, the shell on the positive electrode side is joined to the shell on the negative electrode side via a short circuit prevention gasket and becomes one.
[0341] Below, reference Figure 1 , an all-solid-state secondary battery according to a preferred embodiment of the present invention is described, but the present invention is not limited thereto.
[0342] Figure 1 This is a cross-sectional view schematically showing an all-solid-state secondary battery (lithium-ion secondary battery) according to a preferred embodiment of the present invention. When viewed from the negative electrode side, the all-solid-state secondary battery 10 of this embodiment has a negative electrode collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4, and a positive electrode collector 5 in sequence. Each layer is in contact with each other and has an adjacent structure. By adopting such a structure, electrons (e) are supplied to the negative electrode side during charging. - ) and accumulate lithium ions (Li + On the other hand, during discharge, the lithium ions (Li + ) returns to the positive electrode side, and supplies electrons to the working portion 6. In the example shown in the figure, a light bulb is used as a model in the working portion 6, and the light bulb is lit by discharge.
[0343] In will have Figure 1When the all-solid-state secondary battery with the layer structure shown is placed in a 2032-type button battery case, the all-solid-state secondary battery is sometimes also referred to as an electrode sheet for an all-solid-state secondary battery, and the battery made by placing the all-solid-state secondary battery electrode sheet in a 2032-type button battery case is called an all-solid-state secondary battery.
[0344] (Positive electrode active material layer, solid electrolyte layer, negative electrode active material layer)
[0345] In the all-solid-state secondary battery 10, the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer are all formed by the inorganic solid electrolyte composition of the present invention. The all-solid-state secondary battery 10 shows excellent battery performance. The inorganic solid electrolyte and the polymer binder contained in the positive electrode active material layer 4, the solid electrolyte layer 3 and the negative electrode active material layer 2 can be the same type or different types.
[0346] In the present invention, either or both of the positive electrode active material layer and the negative electrode active material layer are simply referred to as active material layer or electrode active material layer. Also, either or both of the positive electrode active material and the negative electrode active material are simply referred to as active material or electrode active material.
[0347] In the present invention, if the above-mentioned polymer binder A and B are used in combination with solid particles such as inorganic solid electrolytes and active materials, as described above, the cohesiveness of solid particles to each other can be made firm while suppressing the rise of the interface resistance between the solid particles. In addition, the adhesion of solid particles and collector can be improved while suppressing the rise of the interface resistance. Therefore, the all-solid-state secondary battery of the present invention shows excellent battery performance (battery resistance and cycle characteristics).
[0348] In the all-solid-state secondary battery 10, the negative electrode active material layer can be set as a lithium metal layer. As the lithium metal layer, there can be cited a layer formed by stacking or molding lithium metal powder, lithium foil, and lithium vapor-deposited film. The thickness of the lithium metal layer is independent of the thickness of the negative electrode active material layer, and can be set to, for example, 1 to 500 μm.
[0349] The positive electrode current collector 5 and the negative electrode current collector 1 are preferably electron conductors.
[0350] In the present invention, either the positive electrode current collector or the negative electrode current collector, or both of them together, may be simply referred to as a current collector.
[0351] As the material forming the positive electrode collector, in addition to aluminum, aluminum alloy, stainless steel, nickel and titanium, it is preferred to treat the surface of aluminum or stainless steel with carbon, nickel, titanium or silver (forming a thin film), among which aluminum and aluminum alloy are more preferred.
[0352] As the material for forming the negative electrode collector, in addition to aluminum, copper, copper alloys, stainless steel, nickel and titanium, it is preferred to use a material in which the surface of aluminum, copper, copper alloys or stainless steel is treated with carbon, nickel, titanium or silver, and aluminum, copper, copper alloys and stainless steel are more preferred.
[0353] The shape of the current collector is generally a film sheet, but a mesh, a perforated body, a lath body, a porous body, a foamed body, a molded body of a fiber group, or the like may also be used.
[0354] The thickness of the current collector is not particularly limited, but is preferably 1 to 500 μm. It is also preferred that the surface of the current collector be provided with irregularities by surface treatment.
[0355] In the present invention, functional layers, components, etc. may be appropriately inserted or arranged between or outside the negative electrode collector, the negative electrode active material layer, the solid electrolyte layer, the positive electrode active material layer, and the positive electrode collector. Furthermore, each layer may be configured as a single layer or as a multilayer.
[0356] [Method for manufacturing all-solid-state secondary battery]
[0357] All-solid-state secondary batteries can be manufactured by conventional methods. Specifically, all-solid-state secondary batteries can be manufactured by forming the above-mentioned layers using the inorganic solid electrolyte composition of the present invention. In addition, since the dispersion stability of the inorganic solid electrolyte composition of the present invention is excellent, it is not necessary to implement the preparation of the inorganic solid electrolyte composition and the film formation of each layer in chronological order (immediately after preparing the composition), and it is also possible to manufacture an all-solid-state secondary battery that suppresses the degradation of battery performance. In this way, the present invention can manufacture an all-solid-state secondary battery that shows excellent battery performance and preferably shows a small resistance under flexible manufacturing conditions. Below, it is described in detail.
[0358] The all-solid-state secondary battery of the present invention can be manufactured by a method (manufacturing method of a sheet for an all-solid-state secondary battery of the present invention) comprising (via) a step of appropriately coating the inorganic solid electrolyte composition of the present invention on a substrate (e.g., a metal foil serving as a current collector) to form a coating film (film formation).
[0359] For example, an inorganic solid electrolyte composition containing a positive electrode active material as a positive electrode material (positive electrode composition) is applied to a metal foil as a positive electrode collector to form a positive electrode active material layer to make a positive electrode sheet for an all-solid-state secondary battery. Next, a solid electrolyte layer is formed by applying an inorganic solid electrolyte composition for forming a solid electrolyte layer on the positive electrode active material layer. In addition, a negative electrode active material layer is formed by applying an inorganic solid electrolyte composition containing a negative electrode active material as a negative electrode material (negative electrode composition) on the solid electrolyte layer. By overlapping the negative electrode collector (metal foil) on the negative electrode active material layer, an all-solid-state secondary battery having a structure in which a solid electrolyte layer is sandwiched between the positive electrode active material layer and the negative electrode active material layer can be obtained. It can also be enclosed in a housing as a desired all-solid-state secondary battery.
[0360] Furthermore, in contrast to the method of forming each layer, an all-solid-state secondary battery can be manufactured by forming a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer on a negative electrode collector and stacking the positive electrode collector.
[0361] As other methods, the following methods can be cited. That is, a positive electrode sheet for an all-solid-state secondary battery is prepared as described above. In addition, an inorganic solid electrolyte composition containing a negative electrode active material is applied as a negative electrode material on a metal foil as a negative electrode collector to form a negative electrode active material layer to prepare a negative electrode sheet for an all-solid-state secondary battery. Next, on the active material layer of any one of these sheets, a solid electrolyte layer is formed as described above. Moreover, on the solid electrolyte layer, another of the positive electrode sheet for an all-solid-state secondary battery and the negative electrode sheet for an all-solid-state secondary battery are stacked in such a manner that the solid electrolyte layer is in contact with the active material layer. In this way, an all-solid-state secondary battery can be manufactured.
[0362] In addition, as other methods, the following methods can be cited. That is, a positive electrode sheet for an all-solid-state secondary battery and a negative electrode sheet for an all-solid-state secondary battery are prepared as described above. In addition, a solid electrolyte sheet for an all-solid-state secondary battery consisting of a solid electrolyte layer is prepared by applying an inorganic solid electrolyte composition to a substrate. Moreover, the solid electrolyte layer peeled off from the substrate is sandwiched by a positive electrode sheet for an all-solid-state secondary battery and a negative electrode sheet for an all-solid-state secondary battery. In this way, an all-solid-state secondary battery can be manufactured.
[0363] The solid electrolyte layer and the like are formed, for example, by pressure-molding an inorganic solid electrolyte composition and the like on a substrate or an active material layer under pressure conditions described later.
[0364] In the above-mentioned production method, the inorganic solid electrolyte-containing composition of the present invention may be used in any of the positive electrode composition, the inorganic solid electrolyte-containing composition, and the negative electrode composition, but preferably all of them are used.
[0365] <Formation of Each Layer (Film Formation)>
[0366] The method for coating the inorganic solid electrolyte composition is not particularly limited and can be appropriately selected, and examples thereof include coating (preferably wet coating), spray coating, spin coating, dip coating, slit coating, stripe coating, and bar coating.
[0367] At this time, the inorganic solid electrolyte composition can be dried after being coated separately, or it can be dried after multi-layer coating. There is no particular restriction on the drying temperature. The lower limit is preferably above 30°C, more preferably above 60°C, and more preferably above 80°C. The upper limit is preferably below 300°C, more preferably below 250°C, and more preferably below 200°C. By heating within such a temperature range, the dispersion medium can be removed to obtain a solid state (coating dry layer). Moreover, the temperature will not be too high and the various components of the all-solid-state secondary battery will not be damaged, so it is preferred. As a result, in the all-solid-state secondary battery, excellent overall performance is exhibited and good adhesion and good ion conductivity can be obtained without pressurization.
[0368] In the present invention, it is preferred to set the drying temperature to a temperature above the crystallization temperature of the polymer forming the polymer binder B contained in the inorganic solid electrolyte composition in order to take into account both the suppression of the increase in interface resistance and the strong adhesion between the solid particles at a higher level. The drying temperature at this time is not particularly limited as long as it is above the crystallization temperature of the polymer and can be set appropriately. For example, the crystallization temperature can be set to +3°C, and the crystallization temperature can be further set to +10°C. In this way, it is preferred to heat the inorganic solid electrolyte composition at a prescribed temperature and then cool it by a conventional method. Thus, the crystalline component of the polymer is temporarily melted and then recrystallized, so that the adhesion between the solid particles can be made strong while maintaining the interface contact state.
[0369] As described above, when the inorganic solid electrolyte-containing composition of the present invention is applied and dried, the solid particles are firmly bonded together and a coated and dried layer having a low interface resistance between the solid particles can be formed.
[0370] Preferably, after applying the inorganic solid electrolyte composition, each layer or the all-solid-state secondary battery is pressurized after overlapping the constituent layers or after making the all-solid-state secondary battery. In addition, it is also preferred to pressurize in a state where each layer is stacked. As a pressurization method, a hydraulic cylinder punching machine and the like can be cited. There is no particular limitation on the pressure, and it is usually preferably in the range of 5 to 1500 MPa.
[0371] Furthermore, the coated inorganic solid electrolyte composition can be heated while being pressurized. There is no particular limitation on the heating temperature, but generally, it is in the range of 30 to 300°C. It is also possible to perform stamping at a temperature higher than the glass transition temperature of the inorganic solid electrolyte. On the other hand, when the inorganic solid electrolyte and the polymer binder coexist, it is also possible to perform pressing at a temperature higher than the glass transition temperature of the polymer binder. However, it is generally a temperature not exceeding the melting point of the above-mentioned polymer binder.
[0372] The pressurization may be performed in a state where the coating solvent or dispersion medium is dried in advance, or may be performed in a state where the solvent or dispersion medium remains.
[0373] In addition, the respective compositions may be applied simultaneously, or applied, dried, and pressed simultaneously and / or sequentially. After being applied to respective substrates, the compositions may be laminated by transfer.
[0374] The environment during coating and pressurization is not particularly limited, and may be any environment such as atmospheric pressure, dry air (dew point -20°C or lower), or an inert gas (e.g., argon, helium, or nitrogen).
[0375] The punching time can be a short time (e.g., within a few hours) to apply high pressure, or a long time (more than 1 day) to apply moderate pressure. In addition to the sheet for all-solid-state secondary batteries, for example, in the case of all-solid-state secondary batteries, it is possible to use a restraining tool (screw tightening pressure, etc.) of the all-solid-state secondary battery to continuously apply moderate pressure.
[0376] The pressing pressure may be uniform or different relative to the pressure receiving portion such as the sheet surface.
[0377] The pressing pressure can be changed according to the area or thickness of the pressure receiving portion, and the same portion can also be changed in stages with different pressures.
[0378] The stamping surface can be smooth or rough.
[0379] <Initialization>
[0380] The all-solid-state secondary battery manufactured in the above manner is preferably initialized after manufacturing or before use. There is no particular limitation on initialization, for example, initial charging and discharging can be performed under an increased stamping pressure, and then the pressure is released until the general use pressure of the all-solid-state secondary battery is reached.
[0381] [Applications of all-solid-state secondary batteries]
[0382] The all-solid-state secondary battery of the present invention can be applied to a variety of purposes. The applicable mode is not particularly limited. For example, when it is mounted on an electronic device, a notebook computer, a pen input computer, a mobile computer, an e-book reader, a mobile phone, a wireless telephone sub-machine, a pager, a handheld terminal, a portable fax machine, a portable copier, a portable printer, a stereo headset, a camcorder, a liquid crystal television, a portable vacuum cleaner, a portable CD, a small disk, an electric shaver, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, etc. As other civilian products, automobiles, electric vehicles, motors, lighting fixtures, toys, game consoles, load regulators, clocks, flashlights, cameras, and medical equipment (pacemakers, hearing aids, and shoulder massagers, etc.) can be listed. Moreover, it can be used as various military products and aviation products. Moreover, it can also be combined with solar cells.
[0383] The present invention will be described in further detail below with reference to the Examples, but the present invention is not limited thereto and should not be construed. In the following Examples, "parts" and "%" representing the composition are by mass unless otherwise specified. In the present invention, "room temperature" means 25°C.
[0384] 1. Synthesis of polymers used in examples and comparative examples and preparation of polymer binder dispersions, etc.
[0385] The (meth)acrylic polymer A (referred to as “acrylic acid A” in Table 1, Table 2-1, and Table 2-2) is shown below. However, the contents of the constituent components are omitted.
[0386] [Chemical formula 1]
[0387]
[0388] [Synthesis Example 1: Synthesis of Acrylic Polymer A and Preparation of Adhesive Dispersion Liquid Composed of Acrylic Polymer A]
[0389] To a 2L three-necked flask with a reflux cooling tube and a gas introduction plug, 7.2 g of a 40% by mass heptane solution of the following macromonomer M-1, 12.4 g of methyl acrylate (MA), 6.7 g of acrylic acid (AA), 207 g of heptane (manufactured by Wako Pure Chemical Corporation), and 1.4 g of azoisobutyronitrile were added, and nitrogen was introduced at a flow rate of 200 mL / min for 10 minutes, and then the temperature was raised to 100°C. A liquid prepared in a separate container (a liquid mixed with 846 g of a 40% by mass heptane solution of the macromonomer M-1, 222.8 g of methyl acrylate, 75.0 g of acrylic acid, 300.0 g of heptane, and 2.1 g of azoisobutyronitrile) was added dropwise over 4 hours. After the addition was completed, 0.5 g of azoisobutyronitrile was added. Then, after stirring at 100°C for 2 hours, the mixture was cooled to room temperature and filtered to obtain a dispersion of acrylic polymer A. The solid content concentration was 39.2%. The SP value of the (meth)acrylic polymer A was 20.0.
[0390] (Synthesis Example of Macromonomer M-1)
[0391] A macromonomer M-1 was obtained by reacting a self-condensate (GPC polystyrene standard number average molecular weight: 2,000) of glycidyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 12-hydroxystearic acid (manufactured by Wako Pure Chemical Corporation), and polymerizing the macromonomer with methyl methacrylate and glycidyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) at a ratio of 1:0.99:0.01 (molar ratio) and acrylic acid (manufactured by FUJIFILM Wako Pure Chemical Corporation). The SP value of the macromonomer M-1 was 9.3, and the number average molecular weight was 11,000. The SP value and number average molecular weight of the macromonomer are the values calculated by the above method.
[0392] [Synthesis Example 2: Synthesis of Fluoropolymer PVDF-HFP1 and Preparation of Polymer Binder Solution Composed of PVDF-HFP1]
[0393] A fluorine-based polymer PVDF-HFP1 was synthesized, and a binder solution (concentration: 10% by mass) composed of the fluorine-based polymer was prepared.
[0394] Specifically, 200 parts by mass of ion exchange water and 100 parts by mass of vinylidene fluoride were added to the autoclave, and 1 part by mass of diisopropyl peroxydicarbonate was added, and stirred at 30°C for 24 hours. After the polymerization was completed, 25 parts by mass of hexafluoropropylene and 1 part by mass of diisopropyl peroxydicarbonate were added to the reaction mixture, and stirred at 30°C for 24 hours. After the polymerization was completed, the precipitate was filtered and dried at 100°C for 10 hours, thereby obtaining PVDF-HFP1 (polymer binder). The obtained PVDF-HFP1 was dissolved in butyl butyrate to obtain a binder solution.
[0395] PVDF-HFP1 is a block copolymer of polyvinylidene fluoride (PVdF) and hexafluoropropylene (HFP) with a copolymerization ratio [PVdF:HFP] (mass ratio) of 80:20, and has an SP value of 11.4.
[0396] [Synthesis Example 3: Synthesis of Fluoropolymer PVDF-HFP2 and Preparation of Polymer Binder Solution Composed of PVDF-HFP2]
[0397] Fluorine-based polymer PVDF-HFP2 was synthesized in the same manner as PVDF-HFP1 except that vinylidene fluoride was changed to 93.8 parts by mass and hexafluoropropylene was changed to 31.3 parts by mass. The obtained PVDF-HFP2 was dissolved in butyl butyrate to obtain a binder solution (concentration 10% by mass).
[0398] PVDF-HFP2 is a block copolymer of polyvinylidene fluoride (PVdF) and hexafluoropropylene (HFP) with a copolymerization ratio [PVdF:HFP] (mass ratio) of 75:25, and has an SP value of 12.0.
[0399] [Synthesis Example 4: Synthesis of Fluoropolymer PVDF-HFP3 and Preparation of Polymer Binder Solution Composed of PVDF-HFP3]
[0400] 200 parts by mass of ion exchange water, 100 parts by mass of vinylidene fluoride, 25 parts by mass of hexafluoropropylene were added to the autoclave, and 2 parts by mass of diisopropyl peroxydicarbonate were added, and stirred at 70°C for 24 hours. After the polymerization was completed, the precipitate was filtered and dried at 100°C for 10 hours to obtain PVDF-HFP3 (polymer binder). The obtained PVDF-HFP3 was dissolved in butyl butyrate to obtain a binder solution (concentration 10% by mass).
[0401] PVDF-HFP3 is a random copolymer of polyvinylidene fluoride (PVdF) and hexafluoropropylene (HFP) with a copolymerization ratio [PVdF:HFP] (mass ratio) of 80:20, and has an SP value of 11.4.
[0402] [Synthesis Example 5: Synthesis of Fluoropolymer PVDF-HFP4 and Preparation of Polymer Binder Solution Composed of PVDF-HFP4]
[0403] PVDF-HFP4 was synthesized in the same manner as in Synthesis Example 2 except that vinylidene fluoride was changed to 90 parts by mass and hexafluoropropylene was changed to 10 parts by mass. The obtained PVDF-HFP4 was dissolved in butyl butyrate to obtain a binder solution (concentration 10% by mass).
[0404] PVDF-HFP4 is a block copolymer of polyvinylidene fluoride (PVdF) and hexafluoropropylene (HFP) with a copolymerization ratio [PVdF:HFP] (mass ratio) of 90:10, and has an SP value of 10.2.
[0405] [Synthesis Example 6: Synthesis of Fluoropolymer PVDF-HFP5 and Preparation of Polymer Binder Solution Composed of PVDF-HFP5]
[0406] PVDF-HFP5 was synthesized in the same manner as in Synthesis Example 2 except that vinylidene fluoride was changed to 85 parts by mass and hexafluoropropylene was changed to 15 parts by mass. The obtained PVDF-HFP5 was dissolved in butyl butyrate to obtain a binder solution (concentration 10% by mass).
[0407] PVDF-HFP5 is a block copolymer of polyvinylidene fluoride (PVdF) and hexafluoropropylene (HFP) with a copolymerization ratio [PVdF:HFP] (mass ratio) of 85:15, and has an SP value of 10.8.
[0408] [Synthesis Example 7: Synthesis of Fluoropolymer PVDF-HFP6 and Preparation of Polymer Binder Dispersion Liquid Composed of PVDF-HFP6]
[0409] 200 parts by mass of ion exchange water and 85 parts by mass of vinylidene fluoride were added to the autoclave, and 1 part by mass of diisopropyl peroxydicarbonate was added, and stirred at 40°C for 72 hours. After the polymerization was completed, 15 parts by mass of hexafluoropropylene and 1 part by mass of diisopropyl peroxydicarbonate were added to the reaction mixture, and stirred at 40°C for 72 hours. After the polymerization was completed, the precipitate was filtered and dried at 100°C for 10 hours to obtain PVDF-HFP6 (polymer binder). The obtained PVDF-HFP6 was dispersed in butyl butyrate to obtain a binder dispersion (concentration 10% by mass).
[0410] PVDF-HFP6 is a block copolymer of polyvinylidene fluoride (PVdF) and hexafluoropropylene (HFP) with a copolymerization ratio [PVdF:HFP] (mass ratio) of 85:15, and has an SP value of 10.8. The average particle size of the polymer binder composed of this polymer in the inorganic solid electrolyte composition is 1.0 μm.
[0411] [Synthesis Example 8: Synthesis of hydrocarbon polymer CEBC and preparation of polymer binder solution composed of CEBC]
[0412] A hydrocarbon-based polymer CEBC was synthesized, and a binder solution composed of the hydrocarbon-based polymer was prepared.
[0413] Specifically, 150 parts by mass of toluene, 60 parts by mass of 1,3-butadiene, 30 parts by mass of ethylene were added to the autoclave, and 1 part by mass of polymerization initiator V-601 (manufactured by Wako Pure Chemical Industries, Ltd.) was added, the temperature was raised to 80°C, and stirred for 3 hours. After that, 10 parts by mass of propylene and 1 part by mass of V-601 were added, the temperature was raised to 80°C, and stirred for 3 hours. Then, the temperature was raised to 90°C, and the reaction was carried out until the conversion rate reached 100%. The obtained solution was precipitated into methanol again, and the obtained solid was dried to obtain a polymer. The mass average molecular weight of the polymer was 83,000. Then, 50 parts by mass of the polymer obtained above was dissolved in 50 parts by mass of cyclohexane and 150 parts by mass of THF (tetrahydrofuran), and the solution was set to 70° C., 3 parts by mass of n-butyl lithium, 3 parts by mass of 2,6-di-tert-butyl-p-cresol, 1 part by mass of bis(cyclopentadienyl)titanium dichloride and 2 parts by mass of diethylaluminum chloride were added, and the mixture was stirred at a hydrogen pressure of 10 kg / cm 2 The reaction was continued for 1 hour, and CEBC was obtained by distillation and drying. The mass average molecular weight of CEBC was 83,000.
[0414] The obtained CEBC was dissolved in butyl butyrate to prepare a binder solution having a concentration of 10% by mass.
[0415] The block copolymer of CEBC has a copolymerization ratio (mass ratio) of propylene, ethylene and butene of 10:30:60 and an SP value of 17.0.
[0416] [Preparation Example 1: Preparation of a polymer binder dispersion composed of a fluorine-based polymer PVDF]
[0417] PVDF: Polyvinylidene fluoride (trade name, mass average molecular weight 180,000, manufactured by Sigma Aldrich, SP value 23.2) was dissolved in butyl butyrate to prepare a polymer binder dispersion having a solid content concentration of 10% by mass.
[0418] [Preparation Example 2: Preparation of a polymer binder solution composed of a hydrocarbon polymer SEBS]
[0419] SEBS: A styrene-ethylene-butylene-styrene block copolymer (SEBS, mass average molecular weight 100,000, manufactured by Sigma Aldrich, SP value 18.0) was dissolved in butyl butyrate to prepare a polymer binder solution having a solid content concentration of 10% by mass.
[0420] [Preparation Example 3: Preparation of a polymer binder solution composed of a hydrocarbon polymer SBR]
[0421] SBR: Hydrogenated styrene butadiene rubber (DYNARON 1321P (trade name), mass average molecular weight 230,000, manufactured by JSR Corporation, SP value 16.6) was dissolved in butyl butyrate to prepare a polymer binder solution having a solid content concentration of 10% by mass.
[0422] [Preparation Example 4: Preparation of a polymer binder dispersion composed of acrylic microparticles]
[0423] Into a 45 mL container made of zirconium oxide (manufactured by Fritsch Co., Ltd.), 180 g of zirconium oxide beads with a diameter of 5 mm were added, and 5 g of acrylic fine particles (trade name: TAFTIC FH-S005) and 45 g of butyl butyrate were added, and the mixture was placed in a planetary ball mill P-7 manufactured by Fritsch Co., Ltd. The mixture was mixed at a temperature of 25° C. and a rotation speed of 200 rpm for 15 minutes to prepare a polymer binder dispersion composed of acrylic fine particles with a solid content concentration of 10% by mass.
[0424] The presence or absence of crystalline components, crystallization temperature and mass average molecular weight of each polymer forming the polymer binder are shown in Table 1. The mass average molecular weight of each polymer was measured by the above method (condition 2). In addition, the crystallization temperature of each polymer binder was measured by the above method.
[0425] [Table 1]
[0426]
[0427] For each of the prepared polymer binders, the adsorption rate (A) of the inorganic solid electrolytes shown in Table 2-1 and Table 2-2 (collectively referred to as Table 2) was measured by the following method. SE ), the adsorption rate (A) of the active substances (active substances used to prepare the composition) shown in Table 2 AM ), solubility in non-polar dispersion media, and peel strength to copper foil or aluminum foil. In addition, the average particle size of the particulate polymer binder was measured by the above method. The results are shown in Table 2.
[0428] [Synthesis Example A: Synthesis of Sulfide-based Inorganic Solid Electrolyte]
[0429] The sulfide-based inorganic solid electrolyte was synthesized with reference to the non-patent literature of T. Ohtomo, A. Hayashi, M. Tatsumisago, Y. Tsuchida, S. Hama, K. Kawamoto, Journal of Power Sources, 233, (2013), pp231-235 and A. Hayashi, S. Hama, H. Morimoto, M. Tatsumisago, T. Minami, Chem. Lett., (2001), pp872-873.
[0430] Specifically, 2.42 g of lithium sulfide (Li2S, manufactured by Aldrich. Inc., purity>99.98%) and 3.90 g of phosphorus pentasulfide (P2S5, manufactured by Aldrich. Inc., purity>99%) were weighed in a glove box under an argon atmosphere (dew point -70°C), put into an agate mortar, and mixed for 5 minutes using an agate pestle. The mixing ratio of Li2S and P2S5 was set to Li2S:P2S5=75:25 in terms of molar ratio.
[0431] 66 g of zirconia beads with a diameter of 5 mm were added to a 45 mL zirconia container (manufactured by Fritsch Co., Ltd.), and the total amount of the mixture of the above-mentioned lithium sulfide and phosphorus pentasulfide was added, and the container was completely sealed under an argon atmosphere. The container was set in a planetary ball mill P-7 (trade name, manufactured by Fritsch Co., Ltd.), and mechanical grinding was performed for 20 hours at a temperature of 25°C and a rotation speed of 510 rpm to obtain 6.20 g of a yellow powdered sulfide-based inorganic solid electrolyte (Li-PS-based glass, hereinafter sometimes labeled as LPS). The average particle size of the Li-PS-based glass is 2.5 μm.
[0432] [Adsorption rate of polymer binder to inorganic solid electrolyte A SE Determination of
[0433] 0.5 g of inorganic solid electrolyte (LPS) and 0.26 g of polymer binder used to prepare each inorganic solid electrolyte composition shown in Table 2 were placed in a 15 mL medicine bottle, 25 g of butyl butyrate was added while stirring with a mixing rotor, and further stirred at 80 rpm for 30 minutes at room temperature. The stirred dispersion was filtered through a filter with a pore size of 1 μm, 2 g of the filtrate was dried, and the mass BX of the dried polymer binder (the mass of the polymer binder not adsorbed on the inorganic solid electrolyte) was measured.
[0434] The adsorption rate of the polymer binder to the inorganic solid electrolyte was calculated by the following formula from the mass BX of the polymer binder obtained in this way and the mass 0.26 g of the polymer binder used.
[0435] Adsorption rate of polymer binder A SE The above measurement was performed twice and the adsorption rate was taken as an average value.
[0436] Adsorption rate (%) = [(0.26-BX×25 / 2) / 0.26]×100
[0437] In addition, the adsorption rate A was measured using the inorganic solid electrolyte and the polymer binder taken out from the formed inorganic solid electrolyte layer. SE The results obtained the same value.
[0438] [Adsorption rate of polymer binder to active substances A AM Determination of
[0439] 1.6 g of active material and 0.08 g of polymer binder for preparing each inorganic solid electrolyte composition (electrode composition) shown in Table 2 were placed in a 15 mL medicine bottle, 8 g of butyl butyrate was added while stirring with a mixing rotor, and further stirred at 80 rpm for 30 minutes at room temperature. The stirred dispersion was filtered through a filter with a pore size of 1 μm, 2 g of the filtrate was dried, and the mass of the dried polymer binder (the mass of the polymer binder not adsorbed on the active material) was measured.
[0440] The adsorption rate of the polymer binder to the active material was calculated by the following formula from the mass BY of the polymer binder obtained in this way and the mass 0.08 g of the polymer binder used.
[0441] Adsorption rate of polymer binder A AM The above measurement was performed twice and the adsorption rate was taken as an average value.
[0442] Adsorption rate (%) = [(0.08-BY×8 / 2) / 0.08]×100
[0443] In addition, the adsorption rate A was measured using the active material and the polymer binder taken out from the film-formed active material layer. AM The results obtained the same value.
[0444] [Determination of solubility in non-polar dispersion media]
[0445] A predetermined amount of each polymer binder was weighed into a glass bottle, 100 g of butyl butyrate was added, and the mixture was stirred at 80 rpm for 24 hours at 25° C. The transmittance of the mixed solution obtained after stirring for 24 hours was measured under the following conditions.
[0446] This test (transmittance measurement) was performed by changing the amount of polymer binder dissolved, and the upper limit concentration X (mass %) at which the transmittance became 99.8% was defined as the solubility of the polymer binder in the nonpolar dispersion medium.
[0447] <Transmittance Measurement Conditions>
[0448] Dynamic light scattering (DLS) measurement
[0449] Device: DLS measurement device DLS-8000 manufactured by Otsuka Electronics Co., Ltd.
[0450] Laser wavelength, output: 488nm / 100mW
[0451] Sample cell: NMR tube
[0452] [Measurement of peel strength (90° peel test) of current collector (copper foil or aluminum foil)]
[0453] A solution (solid content concentration: 10% by mass) obtained by dissolving each adhesive in a dispersant (DIBK) was dropped onto a copper foil (trade name: C1100, manufactured by Hohsen Corp.) or an aluminum foil (trade name: A1N30, manufactured by Hohsen Corp.) and then dried (temperature: 100°C, time: 180 minutes) to produce a dry film (width: 10 mm, length: 50 mm) with a thickness of 50 μm.
[0454] The average peeling force when the obtained dry film was peeled off from the coated surface of the copper foil at an angle of 90° at a speed of 30 mm / s using a tensile tester (ZTS-50N, manufactured by IMADA CO., LTD.) was taken as the peel strength (unit: N / mm).
[0455] In addition, the peel strength of each polymer binder used in positive electrode compositions P-1 to P-21 to aluminum foil was measured, and the peel strength of each polymer binder used in negative electrode compositions N-1 to N-4 to copper foil was measured.
[0456] [Example 1]
[0457] In Example 1, an inorganic solid electrolyte-containing composition, a negative electrode composition, and a positive electrode composition were prepared using the prepared or provided polymer binder, and their dispersibility was evaluated.
[0458] <Preparation of Positive Electrode Composition No. P-1>
[0459] Into a 45 mL zirconia container (manufactured by Fritsch Co., Ltd.), 160 g of zirconia beads with a diameter of 5 mm were added, and 2.09 g of LPS synthesized in Synthesis Example A and 12.3 g of butyl butyrate as a dispersion medium were added. The container was set in a planetary ball mill P-7 manufactured by Fritsch Co., Ltd. and mixed at a temperature of 25°C and a rotation speed of 300 rpm for 2 hours. Then, NMC (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, average particle size 3.0μm) 7.11g, acetylene black 0.19g, as polymer binder A, the binder dispersion of acrylic particles (trade name: TAFTICFH-S005) with a solid content conversion of 0.047g, as polymer binder B, the binder solution of PVDF-HFP1 prepared in Synthesis Example 2 with a solid content conversion of 0.047g, is similarly set in a planetary ball mill P-7, and mixed for 15 minutes at a temperature of 25°C and a rotation speed of 200rpm. In this way, a positive electrode composition (slurry) No. P-1 was prepared.
[0460] <Preparation of Positive Electrode Composition Nos. P-2 to P-21>
[0461] In the preparation of positive electrode composition No. P-1, the dispersion or content (solid content) of polymer binder A, the solution or content (solid content) of polymer binder B, and further the inorganic solid electrolyte, dispersion medium or active material were changed to the contents shown in Table 2. Otherwise, positive electrode compositions No. P-2 to P-21 were prepared in the same manner as the preparation of positive electrode composition No. P-1.
[0462] <Preparation of Inorganic Solid Electrolyte Composition No. S-2>
[0463] 180 g of zirconia beads with a diameter of 5 mm were placed in a 45 mL container made of zirconia (manufactured by Fritsch Co., Ltd.), and 1.93 g of LPS synthesized in Synthesis Example A and 12.3 g of butyl butyrate as a dispersion medium were placed. Then, a binder dispersion of 0.03 g of acrylic microparticles (trade name: TAFTIC FH-S005) in terms of solid content as polymer binder A and a binder solution of 0.03 g of PVDF-HFP1 prepared in Synthesis Example 2 in terms of solid content as polymer binder B were placed in the container and set in a planetary ball mill P-7 manufactured by Fritsch Co., Ltd. The mixture was mixed at a temperature of 25° C. and a rotation speed of 200 rpm for 15 minutes to prepare an inorganic solid electrolyte composition No. S-2.
[0464] <Preparation of Inorganic Solid Electrolyte Compositions No. S-1, S-3 and S-4>
[0465] In the preparation of inorganic solid electrolyte composition No. S-2, the dispersion or content (solid content) of polymer binder A, the solution or content (solid content) of polymer binder B, etc. were changed to the contents shown in Table 2. In addition, inorganic solid electrolyte compositions No. S-1, S-3 and S-4 were prepared in the same manner as the preparation of inorganic solid electrolyte composition No. S-2.
[0466] <Preparation of Negative Electrode Composition (Slurry) No. N-2>
[0467] Into a 45 mL container made of zirconium oxide (manufactured by Fritsch Co., Ltd.), 180 g of zirconium oxide beads with a diameter of 5 mm were added, and 2.90 g of LPS synthesized in Synthesis Example A and 12.3 g of butyl butyrate as a dispersion medium were added. The container was set in a planetary ball mill P-7 manufactured by Fritsch Co., Ltd., and mixed at a temperature of 25° C. and a rotation speed of 300 rpm for 2 hours. After that, 3.50 g of Si (trade name, Silicon Powder, average particle size 1 to 5 μm, manufactured by Alfa Aesar) as an active material, 0.27 g of acetylene black (trade name, AB powder, manufactured by Denka Company Limited) as a conductive aid, 0.034 g of a binder dispersion of acrylic particles (trade name: TAFTIC FH-S005) as a polymer binder A in terms of solid content, and 0.034 g of a binder solution of PVDF-HFP1 prepared in Synthesis Example 2 as a polymer binder B were added to the container, and the container was similarly set in a planetary ball mill P-7, and mixed at a temperature of 25° C. and a rotation speed of 200 rpm for 15 minutes to prepare a negative electrode composition No. N-2.
[0468] <Preparation of Negative Electrode Compositions No. N-1, N-3 and N-4>
[0469] In the preparation of negative electrode composition No. N-2, the dispersion or content (solid content) of polymer binder A, the solution or content (solid content) of polymer binder B, etc. were changed to the contents shown in Table 2. Otherwise, negative electrode compositions No. N-1, N-3 and N-4 were prepared in the same manner as the preparation of negative electrode composition No. N-2.
[0470]
[0471]
[0472] <Abbreviation of table>
[0473] In the table, “-” indicates that there is no corresponding component.
[0474] The unit of content and solubility is "mass %".
[0475] Adsorption rate A SE and A AM The unit of the average particle size is "μm", the unit of the peel strength is "N / mm", and the unit of the SP value is "MPa 1 / 2 ", the unit of number is "pieces / 10μm 2 ”.
[0476] "Negative electrode" in the "Layer" column indicates a composition for a negative electrode, "Positive electrode" indicates a composition for a positive electrode, and "SE" indicates a composition containing an inorganic solid electrolyte.
[0477] LPS: Li-PS glass synthesized in Synthesis Example A (sulfide-based inorganic solid electrolyte)
[0478] LLZ:Li7La3Zr2O 12 (Oxide-based inorganic solid electrolyte)
[0479] Acrylic fine particles: TAFTIC FH-S005 (trade name, average particle size 5 μm, manufactured by Toyobo Co., Ltd.), no crystalline component, mass average molecular weight 130,000, SP value 20 MPa 1 / 2
[0480] Acrylic acid A: (meth)acrylic polymer A synthesized in Synthesis Example 1
[0481] PVDF: polyvinylidene fluoride (manufactured by Sigma Aldrich)
[0482] PVDF-HFP1: PVDF-HFP1 synthesized in Synthesis Example 2
[0483] PVDF-HFP2: PVDF-HFP2 synthesized in Synthesis Example 3
[0484] PVDF-HFP3: PVDF-HFP3 synthesized in Synthesis Example 4
[0485] PVDF-HFP4: PVDF-HFP4 synthesized in Synthesis Example 5
[0486] PVDF-HFP5: PVDF-HFP5 synthesized in Synthesis Example 6
[0487] PVDF-HFP6: PVDF-HFP6 synthesized in Synthesis Example 7
[0488] CEBC: CEBC synthesized in Synthesis Example 8
[0489] SEBS: Styrene-ethylene-butylene-styrene block copolymer (manufactured by Sigma Aldrich)
[0490] SBR: Hydrogenated styrene butadiene rubber (manufactured by JSR Corporation)
[0491] The state of the polymer binder in the inorganic solid electrolyte-containing composition is shown in the "Form" column of polymer binder A and polymer binder B. Specifically, the case where the polymer binder is dispersed in the dispersion medium in a solid state (i.e., a particulate polymer binder) is marked as "particulate form", and the case where the polymer binder is dissolved in the dispersion medium (i.e., a dissolved polymer binder) is marked as "dissolved form".
[0492] NMC:LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (lithium nickel manganese cobalt oxide)
[0493] NCA:LiNi 0.85 Co 0.10 Al 0.05 O2 (lithium nickel cobalt aluminum oxide)
[0494] Si: Silicon Powder (trade name, particle size 1 to 5 μm, manufactured by Alfa Aesar)
[0495] The initial dispersibility of each of the prepared compositions was evaluated.
[0496] Each composition was placed in a sedimentation tube with an inner diameter of 5 mm, and after standing at 25°C for 24 hours, the distance X of the interface between the clarification (supernatant) separated from the composition and the composition (the state of maintaining a dispersed state after the clarification separation) was measured. Specifically, when the distance from the bottom surface of the sedimentation tube to the surface of the clarified layer (the surface of the inserted composition) is set to 100, the distance X from the bottom surface to the above interface is calculated as a percentage, and the evaluation is performed according to which of the following evaluation criteria is included. The results are shown in Table 3. In this experiment, if the evaluation of the initial dispersibility is above the evaluation level "C", the dispersibility of the composition (dispersibility of the solid particles) is excellent, so it is preferred.
[0497] - Rating -
[0498] AA: 98% or more and 100% or less
[0499] A: 95% or more and less than 98%
[0500] B: 90% or more and less than 95%
[0501] C: 85% or more and less than 90%
[0502] D: less than 85%
[0503] [Evaluation of dispersion stability of composition]
[0504] For each of the prepared compositions, dispersion stability was evaluated.
[0505] Regarding dispersion stability, each composition was placed in a sedimentation tube with an inner diameter of 5 mm, and after standing at 25°C for 72 hours, the distance X of the interface between the clarification (supernatant) separated from the composition and the composition (the state of maintaining the dispersed state after clarification and separation) was measured, and evaluated with the same evaluation criteria as the initial dispersibility. The results are shown in Table 3. In this experiment, if the evaluation of dispersion stability is above the evaluation level "C", the dispersion stability of the composition is excellent (the excellent initial dispersibility of the solid particles can be maintained for a long time), so it is preferred.
[0506] [Example 2]
[0507] In Example 2, the compositions prepared in Example 1 were used to prepare a solid electrolyte sheet for an all-solid-state secondary battery and an electrode sheet for an all-solid-state secondary battery, and an all-solid-state secondary battery was manufactured.
[0508] 1. Manufacturing of all-solid-state secondary batteries
[0509] Immediately after preparation, the above-mentioned compositions (slurries) are used to produce solid electrolyte sheets for all-solid-state secondary batteries and electrode sheets for all-solid-state secondary batteries. Using the solid electrolyte sheets for all-solid-state secondary batteries and electrode sheets for all-solid-state secondary batteries, all-solid-state secondary batteries having a coating of the just-prepared composition as a solid electrolyte layer and an active material layer are respectively manufactured in the following manner.
[0510] <Production of negative electrode sheets No. N-1 to N-4 for all-solid-state secondary batteries>
[0511] The above-mentioned newly prepared negative electrode compositions No. N-1 to N-4 were coated on copper foils with a thickness of 20 μm using the above-mentioned Bayer applicator (trade name: SA-201 Bayer applicator, manufactured by TESTER SANGYO CO,.LTD.), and the negative electrode compositions were heated for 1 hour and dried under the drying temperature conditions shown in Table 2, thereby preparing negative electrode sheets No. N-1 to N-4 for all-solid-state secondary batteries having a laminated structure of negative electrode active material layer / copper foil. The thickness of the negative electrode active material layer was 100 μm.
[0512] <Production of positive electrode sheets No. P-1 to P-21 for all-solid-state secondary batteries>
[0513] The positive electrode compositions No. P-1 to P-21 just prepared were applied to aluminum foils with a thickness of 20 μm by an applicator (trade name: SA-201 Bayer applicator, manufactured by Tester Industry Co., Ltd.), and heated for 1 hour under the drying temperature conditions shown in Table 2 to dry the positive electrode compositions, and positive electrode sheets No. P-1 to P-21 for all-solid-state secondary batteries having a laminated structure of positive electrode active material layer / aluminum foil were prepared. The thickness of the positive electrode active material layer was 100 μm.
[0514] <Production of Solid Electrolyte Sheets No. S-1 to S-4 for All-Solid State Secondary Batteries>
[0515] The inorganic solid electrolyte compositions No. S-1 to S-4 just prepared were applied to aluminum foils with a thickness of 20 μm by an applicator (trade name: SA-201 Bayer applicator, manufactured by Tester Industry Co., Ltd.), and heated for 1 hour under the drying temperature conditions shown in Table 2 to dry the inorganic solid electrolyte compositions, thereby producing solid electrolyte sheets No. S-1 to S-4 for all-solid-state secondary batteries having a laminated structure of solid electrolyte layer / aluminum foil. The thickness of the solid electrolyte layer was 30 μm.
[0516] The number of particulate domains derived from the polymer binder contained in the solid electrolyte layer of the solid electrolyte sheet for all-solid-state secondary batteries, the positive electrode active material layer of the positive electrode sheet for all-solid-state secondary batteries, and the negative electrode active material layer of the negative electrode sheet for all-solid-state secondary batteries (number / 10 μm) was measured by the above method. 2 ). The results are shown in Table 2.
[0517] [Adhesion test of solid electrolyte sheet for all-solid-state secondary battery and electrode sheet for all-solid-state secondary battery (90° peel test)]
[0518] The solid electrolyte sheets for all-solid-state secondary batteries and the electrode sheets for all-solid-state secondary batteries produced using the compositions prepared in Example 1 immediately after preparation were evaluated for the binding properties of the solid electrolyte layers or the active material layers.
[0519] Specifically, a tape (width: 1 cm, length: 5 cm, trade name: polyimide tape, manufactured by Nitto Denko Corporation) was attached (pressed and bonded at a pressure of 0.1 MPa for 5 minutes) to the surface of the solid electrolyte layer or active material layer of each sheet using a tensile testing machine (ZTS-50N, manufactured by IMADA CO., LTD.), and the average peeling force when the tape was peeled off at an angle of 90° to the surface of the solid electrolyte layer or the active material layer at a peeling speed of 100 mm / s or 30 mm / s was set as the peel strength (unit: N / mm).
[0520] The measured peel strength is applied to the following evaluation criteria to evaluate the adhesion of the solid electrolyte layer or the active material layer. In this test, regardless of the peeling speed, if the peeling strength is 0.1N / mm or more (evaluation level A and B), it can be said that the adhesion of the solid particles in the solid electrolyte layer or the active material layer and the adhesion of the active material layer to the collector are excellent. In the present invention, the peel strength is more preferably 0.15N / mm or more (evaluation level A).
[0521] -Evaluation criteria for this experiment (peeling speed 100 mm / s)-
[0522] A: 0.15N / mm or more
[0523] B: 0.10 N / mm or more and less than 0.15 N / mm
[0524] C: 0.05N / mm or more and less than 0.10N / mm
[0525] D: less than 0.05N / mm
[0526] - Previous evaluation standard (peeling speed 30 mm / s) -
[0527] A: 0.15N / mm or more
[0528] B: 0.10 N / mm or more and less than 0.15 N / mm
[0529] C: 0.05N / mm or more and less than 0.10N / mm
[0530] D: less than 0.05N / mm
[0531] [Table 3]
[0532]
[0533] <Manufacturing of negative electrode sheets for all-solid-state secondary batteries (No. C-27 to C-30) for evaluation of batteries>
[0534] Each of the negative electrode sheets for all-solid-state secondary batteries produced was punched into a disc shape with a diameter of 10 mm and placed in a cylinder made of polyethylene terephthalate (PET) with an inner diameter of 10 mm. 30 mg of LPS synthesized in Synthesis Example A was placed on the negative electrode active material layer side of the cylinder, and a stainless steel (SUS) rod with a diameter of 10 mm was inserted from the openings at both ends of the cylinder. A pressure of 350 MPa was applied to the collector side and LPS of the negative electrode sheet for all-solid-state secondary batteries by the SUS rod and pressurized. After temporarily removing the SUS rod on the LPS side, a disc-shaped indium (In) sheet (thickness 20 μm) with a diameter of 9 mm and a disc-shaped lithium (Li) sheet (thickness 20 μm) with a diameter of 9 mm were inserted into the LPS in the cylinder in this order. The removed SUS rod was inserted into the cylinder again and fixed under a pressure of 50 MPa. In this way, an all-solid-state secondary battery (half-cell) having a structure of copper foil (thickness 20 μm)-negative electrode active material layer (thickness 80 μm)-solid electrolyte layer (thickness 200 μm)-counter electrode layer (In / Li sheet, thickness 30 μm) was obtained.
[0535] <Manufacturing of positive electrode sheets for all-solid-state secondary batteries (No. C-1 to C-22) for evaluation of batteries>
[0536] Each positive electrode sheet for all-solid-state secondary batteries was punched into a disc shape with a diameter of 10 mm and placed in a PET cylinder with an inner diameter of 10 mm. 30 mg of LPS synthesized in Synthesis Example A was placed on the positive electrode active material layer side of the cylinder, and a SUS rod with a diameter of 10 mm was inserted from the openings at both ends of the cylinder. A pressure of 350 MPa was applied to the collector side and LPS of the positive electrode sheet for all-solid-state secondary batteries by the SUS rod and pressurized. After temporarily removing the SUS rod on the LPS side, a disc-shaped In sheet with a diameter of 9 mm (thickness 20 μm) and a disc-shaped Li sheet with a diameter of 9 mm (thickness 20 μm) were inserted into the LPS in the cylinder in this order. The removed SUS rod was inserted into the cylinder again and fixed under a pressure of 50 MPa. In this way, an all-solid-state secondary battery (half-cell) having a structure of aluminum foil (thickness 20 μm)-positive electrode active material layer (thickness 80 μm)-solid electrolyte layer (thickness 200 μm)-counter electrode layer (In / Li sheet, thickness 30 μm) was obtained.
[0537] (Manufacture of batteries for evaluation of solid electrolyte sheets for all-solid-state secondary batteries (No. C-23 to C-26))
[0538] The positive electrode sheet (No.P-2) for all-solid-state secondary batteries was punched into a disc shape with a diameter of 10 mm and placed in a PET cylinder with an inner diameter of 10 mm. Each solid electrolyte sheet for all-solid-state secondary batteries made on the positive electrode active material layer side of the cylinder was punched into a disc shape with a diameter of 10 mm and placed in the cylinder, and a 10 mm SUS rod was inserted from the openings at both ends of the cylinder. A pressure of 350 MPa was applied to the collector side of the positive electrode sheet for all-solid-state secondary batteries and the aluminum foil side of the solid electrolyte sheet for all-solid-state secondary batteries by the SUS rod and pressurized. The SUS rod on the side of the solid electrolyte sheet for all-solid-state secondary batteries was temporarily removed and the aluminum foil of the solid electrolyte sheet for all-solid-state secondary batteries was gently peeled off, and then a disc-shaped In sheet (thickness 20 μm) with a diameter of 9 mm and a disc-shaped Li sheet (thickness 20 μm) with a diameter of 9 mm were inserted into the LPS in the cylinder in sequence. The removed SUS rod was inserted into the cylinder again and fixed under a pressure of 50 MPa. Thus, an all-solid-state secondary battery (half-cell) having a structure of aluminum foil (thickness 20 μm)-positive electrode active material (80 μm)-solid electrolyte layer (thickness 25 μm)-counter electrode layer (In / Li sheet, thickness 30 μm) was obtained.
[0539] [Evaluation of battery performance (cycle characteristics)]
[0540] Using the all-solid secondary battery manufactured in the above “1. Manufacturing of all-solid secondary battery”, charge and discharge (initialization) at 4.3 V to 3.0 V were performed once at 30° C. with a charge current value of 0.13 mA and a discharge current value of 0.13 mA.
[0541] Then, as a cycle test, the charge and discharge current value was set at 11.7 mA or 0.39 mA under the same conditions in an environment of 25° C., and charge and discharge at 4.3 V to 3.0 V were repeated. One charge and discharge was defined as one cycle.
[0542] During charge and discharge at the same charge and discharge current value, the discharge capacity of the 1st cycle and the discharge capacity of the 20th cycle were measured, and the discharge capacity retention rate was calculated using the following formula. The discharge capacity retention rate was applied to the following evaluation criteria to evaluate the cycle characteristics of the all-solid-state secondary battery.
[0543] In this test, any value of the charge and discharge current is considered acceptable if the evaluation level is "C" or above.
[0544] Discharge capacity retention rate (%) = (discharge capacity at the 20th cycle / discharge capacity at the 1st cycle) × 100
[0545] -Evaluation criteria for this experiment (charge and discharge current value 11.7mA)-
[0546] AA: 80% or more and 100% or less
[0547] A: 70% or more and less than 80%
[0548] B: 60% or more and less than 70%
[0549] C: 50% or more and less than 60%
[0550] D: less than 50%
[0551] - Conventional evaluation standard (charge and discharge current value 0.39mA) -
[0552] AA: 80% or more and 100% or less
[0553] A: 70% or more and less than 80%
[0554] B: 60% or more and less than 70%
[0555] C: 50% or more and less than 60%
[0556] D: less than 50%
[0557] [Evaluation of battery performance (battery resistance)]
[0558] In the battery after 20 cycles in the cycle characteristics at each charge and discharge current value, the voltage was adjusted to 3.8 V, and impedance measurement was performed at an amplitude of 10 mV and a frequency of 100 mHz to 1 MHz to measure the reaction resistance. In this experiment, for any battery after the cycle test, "C" or above was considered acceptable.
[0559] -Evaluation criteria for this experiment (after cycle test at a charge and discharge current value of 11.7 mA)-
[0560] A: Less than 20Ω
[0561] B: 20Ω or more and less than 30Ω
[0562] C: 30Ω or more and less than 40Ω
[0563] D: 40Ω or more
[0564] - Conventional evaluation standard (after cycle test at charge and discharge current value of 0.39 mA) -
[0565] A: Less than 20Ω
[0566] B: 20Ω or more and less than 30Ω
[0567] C: 30Ω or more and less than 40Ω
[0568] D: 40Ω or more
[0569] [Table 4]
[0570]
[0571] The following can be seen from the results shown in Tables 2 to 4.
[0572] That is, the all-solid-state secondary battery in which all layers of the constituent layers and the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer formed by the inorganic solid electrolyte composition of the comparative example, which do not contain the two polymer binders specified in the present invention, are layers not containing the two polymer binders specified in the present invention, etc., has poor adhesion, cycle characteristics and battery resistance in the evaluation criteria of this experiment (expressed as the experimental benchmark in the table.). In addition, the inorganic solid electrolyte composition of the comparative example has a tendency to have poor dispersibility.
[0573] In contrast, the constituent layers formed using the inorganic solid electrolyte composition of the present invention, which contain the two polymer binders specified in the present invention, all show high adhesion in the evaluation criteria of this experiment. In addition, the constituent layers formed using the inorganic solid electrolyte composition of the present invention are suitable for all-solid-state secondary batteries having at least one layer among the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer. In the evaluation criteria of this experiment, the battery resistance is low and excellent cycle characteristics are shown. In addition, the inorganic solid electrolyte composition of the present invention shows high dispersibility (initial dispersibility and dispersion stability).
[0574] In particular, if the heating temperature during the application and drying of the inorganic solid electrolyte composition (forming a constituent layer) is set to be higher than the crystallization temperature of the polymer binder B, it is possible to achieve both lower interface resistance of the obtained constituent layer and stronger bonding between solid particles at a higher level.
[0575] Explanation of symbols
[0576] 1-negative electrode collector, 2-negative electrode active material layer, 3-solid electrolyte layer, 4-positive electrode active material layer, 5-positive electrode collector, 6-working part, 10-all-solid-state secondary battery.
Claims
1. An inorganic solid electrolyte composition comprising: an inorganic solid electrolyte having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, a polymer binder, and a dispersion medium, wherein: The polymer binder comprises at least two different polymer binders A and B, The polymer binder A is in particle form. The polymer binder B is a polymer binder composed of a polymer having a crystallization temperature of 60° C. or higher, The dispersion medium is a non-polar dispersion medium, The solubility of the polymer binder B in the non-polar dispersion medium is 2% by mass or more, The solubility of the polymer binder A in the non-polar dispersion medium is 1% by mass or less.
2. The inorganic solid electrolyte composition according to claim 1, wherein The polymer forming the polymer binder B is a fluorine-based polymer, a hydrocarbon-based polymer, a polyurethane or a (meth)acrylic polymer.
3. The inorganic solid electrolyte composition according to claim 1 or 2, wherein: The polymer forming the polymer binder A is polyurethane or a (meth)acrylic polymer. 4 . The inorganic solid electrolyte-containing composition according to claim 1 , further comprising an active material.
5. The inorganic solid electrolyte composition according to claim 4, wherein The polymer binder B has a peel strength of 0.1 N / mm or more with respect to the current collector. 6 . A sheet for an all-solid-state secondary battery, comprising a layer comprising the inorganic solid electrolyte composition according to claim 1 .
7. The all-solid-state secondary battery sheet according to claim 6, wherein: The layer composed of the inorganic solid electrolyte-containing composition is a product obtained by heating and drying the inorganic solid electrolyte-containing composition at a temperature not lower than the crystallization temperature of the polymer binder B.
8. The sheet material for an all-solid-state secondary battery according to claim 6 or 7, wherein: The layer composed of the inorganic solid electrolyte composition is 10 μm thick. 2 The cross-sectional area includes more than 30 particulate regions derived from the polymer binder.
9. An all-solid-state secondary battery, comprising, in sequence, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein: At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer is a layer composed of the inorganic solid electrolyte composition according to any one of claims 1 to 5.
10. A method for manufacturing a sheet for an all-solid-state secondary battery, comprising: A step of forming a membrane using the inorganic solid electrolyte-containing composition according to any one of claims 1 to 5.
11. The method for producing a sheet for an all-solid-state secondary battery according to claim 10, wherein: The inorganic solid electrolyte composition is heated at a temperature higher than the crystallization temperature of the polymer binder B. 12 . A method for producing an all-solid-state secondary battery, comprising the method for producing a sheet for an all-solid-state secondary battery according to claim 10 or 11.
Citation Information
Patent Citations
Latex agglutination reaction measuring instrument
JP1987022066A
Permanent magnet
JP1987062503A
Catalyst carrier and production thereof
JP1990006856A
Four-wheel steering device
JP1991045473A
Distortion compensator
JP1993090844A